Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Spatial Sequential Matching Enhanced Underwater Single-Photon Lidar Imaging Algorithm - Qiguang Zhu; Yuhang Wang; Chenxu Wang; Tian Rong; Buxiao Li; Xiaotian Ying (Journal of Marine Science and Engineering, 2024)
Traditional LiDAR and air-medium-based single-photon LiDAR struggle to perform effectively in high-scattering environments. The laser beams are subject to severe medium absorption and multiple scattering phenomena in such conditions, greatly limiting the maximum operational range and imaging quality of the system. The high sensitivity and high temporal resolution of single-photon LiDAR enable high-resolution depth information acquisition under limited illumination power, making it highly suitable for operation in environments with extremely poor visibility. In this study, we focus on the data distribution characteristics of active single-photon LiDAR operating underwater, without relying on time-consuming deep learning frameworks. By leveraging the differences in time-domain distribution between noise and echo signals, as well as the hidden spatial information among echo signals from different pixels, we rapidly obtain imaging results across various distances and attenuation coefficients. We have experimentally verified that the proposed spatial sequential matching enhanced (SSME) algorithm can effectively enhance the reconstruction quality of reflection intensity maps and depth maps in strong scattering underwater environments. Through additional experiments, we demonstrated the algorithm’s reconstruction effect on different geometric shapes and the system’s resolution at different distances. This rapidly implementable reconstruction algorithm provides a convenient way for researchers to preview data during underwater single-photon LiDAR studies.

Autonomous inspection robot for dead laying hens in caged layer house - Weihong Ma; Xingmeng Wang; Simon X. Yang; Xianglong Xue; Mingyu Li; Rong Wang; Ligen Yu; Lepeng Song; Qifeng Li (Computers and Electronics in Agriculture, 2024)

Path planning of greenhouse electric crawler tractor based on the improved A* and DWA algorithms - Huiping Guo; Yi Li; Hao Wang; Chensi Wang; Jiao Zhang; Tingwei Wang; Linrui Rong; Haoyu Wang; Zihao Wang; Yaobin Huo; Shaomeng Guo; Fuzeng Yang (Computers and Electronics in Agriculture, 2024)

Effect of long-term temperature-controlled rearing on growth traits and sexual maturity of common carp (Cyprinus carpio) - Yongming Li; Kuangxin Chen; Bin Gui; Cheng Yang; Libo He; Lanjie Liao; Zuoyan Zhu; Yaping Wang; Rong Huang (Aquaculture, 2024)

Scaled experimental study of a ventilation system featuring partition jet and pit exhaust - Qizhi Yang; Xi Bai; Guoqiang Zhang; Li Rong; Yao Tao; Jiyuan Tu; Jinyong Wang; Zhiru Hu; Jie Chai; Yong Wang (Biosystems Engineering, 2024)

Off-site production of plasma-activated water for efficient disinfection: The crucial role of high valence NOx and new chemical pathways - Zifeng Wang; Xiangyu Wang; Shenghang Xu; Renwu Zhou; Mingyan Zhang; Wanchun Li; Zizhu Zhang; Luge Wang; Jinkun Chen; Jishen Zhang; Li Guo; Dandan Pei; et al. (Water Research, 2024)

Learning-guided cross-sampling for large-scale evolutionary multi-objective optimization - Haofan Wang; Li Chen; Xingxing Hao; Rong Qu; Wei Zhou; Dekui Wang; Wei Liu (Swarm and Evolutionary Computation, 2024)

Influence of soil parameter uncertainties on site ambient noise horizontal to vertical spectral ratio modeling - Jixin Wang; Xiaojun Li; Mianshui Rong; Qingxu Zhao; Xiaoshan Kong (Soil Dynamics and Earthquake Engineering, 2024)

Partial organic substitution increases soil quality and crop yields but promotes global warming potential in a wheat-maize rotation system in China - Gong Wu; Hai-meng Huang; Bei-bei Jia; Lei-lei Hu; Chong-sheng Luan; Qi Wu; Xiao-yu Wang; Xiao-xiao Li; Zhao Che; Zhao-rong Dong; He Song (Soil and Tillage Research, 2024)

Neutral purple soil acidification and mineralogical property changes due to long-term urea application in southwest China - Jun Xie; Dan Wang; Yuanxue Chen; Zhiqi Li; Wencai Dai; Rong Huang; Zifang Wang; Ming Gao (Soil and Tillage Research, 2024)

Contribution, absorption mode, and model prediction of atmospheric deposition to copper and lead accumulation in soybean - Min Li; Haotian Wang; Ziqi Chen; Hailong Liu; Huan Zhao; Xiuting Rong; Ruizhi Xia; Xiaozhi Wang; Jun Zhou (Science of The Total Environment, 2024)

Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Effects of the types and ages of vegetation restoration on land surface roughness in the Eastern Hobq Desert, Northern China - Ji Feng; Yong-Sheng Wu; Li-Yuan Lu; Chasina Xi; Feng-Yan Wu; Chao-Yu Wang; Qiang Yin; Altantuya Dorjsuren; Rong-Liang Jia; Yu Qiao; Yuan-Fa Meng; Jie Yu (Science of The Total Environment, 2024)

Revealing the links between hair metal(loids) and alterations in blood pressure among children in e-waste recycling areas through urinary metabolomics - Hong-Xuan Kuang; Ye Liu; Jia-Rong Wang; Meng-Yang Li; Yang Zhou; Lin-Xue Meng; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Long-term cereal-legume intercropping accelerates soil organic carbon loss in subsoil of dryland - Wei Wang; Guang-Rong Chen; Meng-Ying Li; Yinglong Chen; Yang Wang; Hong-Yan Tao; Hui-Zhi Hou; Muhammad Maqsood Ur Rehman; Muhammad Ashraf; Yajie Song; Levis Kavagi; Bao-Zhong Wang; et al. (Resources, Conservation and Recycling, 2024)

Mechanism of β-MnO2 particle for the peroxymonosulfate activation under electric field: the promoting effect of carbamazepine on Mn(III) and reactive oxygen species production - Shaochun Yuan; Shuquan He; Qingyu Wu; Tuo Wang; Mengyu Li; Rong Liu; Yao Chen; Chuanliang Zhao; Fei Liu; Zhen Liu (Process Safety and Environmental Protection, 2024)

Physio-mechanical properties of loess-paleosol sequences over the past 400 ka and their paleoclimate controlling factors on the central Loess Plateau - Xiaoning Wang; Dapeng Yue; Jingbo Zhao; Lixing Zhang; Rong Liu; Jianing Li; Yueshan Liu (Quaternary Science Reviews, 2024)

Phylogenomic analyses of the pantropical Platycerium Desv. (Platycerioideae) reveal their complex evolution and historical biogeography - Jing Zhao; Chuan-Jie Huang; Li-Ju Jiang; Zhao-Rong He; Shuai Yang; Zhang-Ming Zhu; Liang Zhang; Hong Yu; Xin-Mao Zhou; Jia-Guan Wang (Molecular Phylogenetics and Evolution, 2024)

Deciphering the evolution and biogeography of ant-ferns Lecanopteris s.s - Li-Ju Jiang; Jing Zhao; Jia-Guan Wang; Sven Landrein; Ji-Pu Shi; Chuan-Jie Huang; Miao Luo; Xin-Mao Zhou; Hong-Bin Niu; Zhao-Rong He (Molecular Phylogenetics and Evolution, 2024)

Recycle of residual ammonium from weathered crust elution-deposited rare earth tailings via an efficient combined method of elution, struvite precipitation and on-line adsorption - Kejia Wu; Junxia Yu; Jia Wang; Xiaodi Li; Rong Wang; Zhenyue Zhang; Chunqiao Xiao; Ruan Chi (Journal of Water Process Engineering, 2024)

Effect of zero-valent iron and magnetite on mitigating sulfate and lincomycin stress in anaerobic digestion: microbial succession and antibiotic resistant genes removal - Jing Xie; Jiaxin Zhu; Bolin Min; Rong He; Wenbiao Wang; Li Xie (Journal of Water Process Engineering, 2024)

The correlation between single and mixed trace elements exposure in systemic lupus erythematosus: A case-control study - Rong-Gui Huang; Kai-Di Li; Hong Wu; Yi-Yu Wang; Ya Xu; Xue Jin; Yu-Jie Du; Yi-Yuan Wang; Jing Wang; Zhang-Wei Lu; Bao-Zhu Li (Journal of Trace Elements in Medicine and Biology, 2024)

Applicability analysis of comprehensive drought index based on GRACE data in ten major river basins in China - Rong Wu; Zijun Wang; Chenfeng Cui; Yongxiang Li; Miao Tang; Jiangdong Chu; Renjie Xv; Chenrui Zhu; Shuo Wang; Yuli Li; Chengyuan Zhang; Zhannan Huang (Journal of Hydrology, 2024)

A tumor-pH-responsive phthalocyanine as activatable type I photosensitizer for improved photodynamic immunotherapy - Ling Zhang; Rong-Bin Que; Ting-Ting Ke; Chao Wang; Wei Xie; Hong-Jie Sun; Bi-Yuan Zheng; Mei-Rong Ke; Jian-Dong Huang; Xingshu Li (Journal of Photochemistry and Photobiology B: Biology, 2024)

Comparison of the short- and long-term effects of zinc ions on the anaerobic mesophilic co-digestion of food waste and waste activated sludge: Digester performance, antibiotic resistance gene reduction and the microbial community - Bao-Shan Xing; Yi-Meng Su; Yu-Lin Fu; Yi-Fan Wu; Chen-Hao Yan; Xiaochang C. Wang; Yu-You Li; Rong Chen (Journal of Hazardous Materials, 2024)

Variation profiles, formation mechanisms, and emission risks of brominated flame retardant compounds during cement kiln co-processing of hexabromocyclododecane-containing waste - Xin Li; Yahui Liu; Bingcheng Lin; Guohua Zhu; Jian Wang; Xiao Wang; Yueyao Yang; Shanshan Zhang; Guorui Liu; Rong Jin; Minghui Zheng (Journal of Hazardous Materials, 2024)

Secondary activation on plasma-activated water by plasma-treated cotton for restoring and enhancing disinfection effect - Zifeng Wang; Shenghang Xu; Xiangyu Wang; Dingxin Liu; Wanchun Li; Rusen Zhou; Qiuyi Yue; Pengfei Zhang; Jishen Zhang; Hao Zhang; Li Guo; Dandan Pei; et al. (Journal of Hazardous Materials, 2024)

Construction of Bi5O7I/Bi3O4Br heterojunction with abundant oxygen vacancies to enhance photocatalytic performance - Jian Feng; Xia Ran; Li Wang; Bo Xiao; Keqin Zhang; Jinming Zhu; Zuoji Liu; Chaozhong Li; Xinai Cui; Rong Li; Guangwei Feng (Journal of Environmental Chemical Engineering, 2024)

An end-to-end multi-task network for early prediction of the instrumental intensity and magnitude in the north–south seismic belt of China - Qingxu Zhao; Mianshui Rong; Jixin Wang; Xiaojun Li (Journal of Asian Earth Sciences, 2024)

Origin of the Narenwula quartz vein-type W deposit, Inner Mongolia, China: Insights from geochemistry of hosting granites, fluid inclusions, H-O-S isotopes, and wolframite trace elements - Lin-Wei Wang; De-Hui Zhang; Jia-Jun Liu; Zhu Li; Rong-Zhen Zhang; Xi Diao; Bin Zhang; Guo-Ming Weng (Journal of Asian Earth Sciences, 2024)

Advancing mangrove species mapping: An innovative approach using Google Earth images and a U-shaped network for individual-level Sonneratia apetala detection - Chuanpeng Zhao; Yubin Li; Mingming Jia; Chengbin Wu; Rong Zhang; Chunying Ren; Zongming Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Exploring the dynamic characteristic of typical kombucha induced by symbiotic microbiota succession from four Chinese regions: A comprehensive analytical framework - Shiqi Li; Ruinan Wang; Rong Liu; Leran Wang; Xingnan Wang; Jianping Wei; Yahong Yuan; Tianli Yue; Rui Cai; Zhouli Wang (Food Research International, 2024)

Quality improvement of threadfin bream (Nemipterus virgatus) surimi-gel using soy protein as a natural food additive - Yi-Li Gao; Asami Yoshida; Jin-Yang Liu; Jing Yuan; Shinnosuke Maeda; Youjun Wang; Yan-Rong Jiang; Xiao-Mi Sun; Chao-Ping Chen; Yajun Wang; Tetsuhiko Okajima; Kiyoshi Osatomi (Food Chemistry, 2024)

3DVar sectoral emission inversion based on source apportionment and machine learning - Congwu Huang; Tao Niu; Tijian Wang; Chaoqun Ma; Mengmeng Li; Rong Li; Hao Wu; Yawei Qu; Hongli Liu; Xu Liu (Environmental Pollution, 2024)

Meet-in-metabonomics: Insights into associations between hair heavy metal and adverse child growth in e-waste recycling area - Hong-Xuan Kuang; Meng-Yang Li; Jia-Rong Wang; Jian-Hua Tan; Wen-Yao Liang; Yang Zhou; Yun-Jiang Yu (Environmental Pollution, 2024)

Experimental evaluation of bonded/unbonded prestressed precast concrete joints under repetitive loading scenarios: Seismic performance and retrofit intervention - Hao Fang; Hai-Rong Shi; Xiu-Hang Li; Chun-Lin Wang; Bin Zeng (Engineering Structures, 2024)

Ultra-low temperature heating system based on dual-source solar assisted heat pump using compound parabolic concentrator-capillary tube solar collector - Li Wei Yang; Jin Huan Pu; Rong Ji Xu; Tong Yang; Hua Sheng Wang (Energy and Buildings, 2024)

Deciphering the role of biochar pseudocapacitance strengthening in promoting syntrophic methanogenesis: Microbial capacitance-tropism in propionate metabolism - Danyang Zhao; Lizi Ding; Xuemeng Wang; Qian Li; Feixiang Zan; Yu-You Li; Rong Chen (Chemical Engineering Journal, 2024)

Engineered multienzyme-mimicking 2D bismuthene catalytic nanotriggers enable cascade enzyodynamic-boosted and synergistic GPX4/FSP1-mediated ferroptosis amplification for cancer radiosensitization - Yipengchen Yin; Li Zhu; Tiaoyan Jiang; Rong Chai; Ya Zhang; Tianyu Li; Kai Wang; Sheng Wang; Qin Zhang (Chemical Engineering Journal, 2024)

Long-lasting Zn metal anode coated with an industrially available amorphous InGaZnO layer - Jiadong Wu; Linyu Yang; Shuang Zhou; Shuying Wang; Ablat Abliz; Rong Wu; Kunjie Zhu; Xiaolong Yao; Haibing Li; Jun Wang; Hongyu Mi; Jie Li; et al. (Chemical Engineering Journal, 2024)

Facile engineering of metal–organic framework derived SnO2@NiO core–shell nanocomposites based gas sensor toward superior VOCs sensing performance - Hui Xu; Haoran Zhong; Jinwu Hu; Xianjun Rong; Wenhui Zhang; Yinsheng Wang; Shengjuan Li; Guisheng Li; Ding Wang (Chemical Engineering Journal, 2024)

Correction: Developing Estimation Equations for the Cerchar Abrasivity Index of Rocks Applicable to TBM Tunnels - Lei She; Yan-long Li; She-rong Zhang; Chao Wang; Sun-wen He; Yu-jie Wang; Ming-ming He; Sheng-le Wang (Rock Mechanics and Rock Engineering, 2024)

p-Smad3 differentially regulates the cytological behavior of osteoclasts before and after osteoblasts maturation - Jiapeng Ye; Zhen Hua; Jirimutu Xiao; Yang Shao; Shaoshuo Li; Heng Yin; Mao Wu; Yi Rong; Bowen Hong; Yang Guo; Yong Ma; Jianwei Wang (Molecular Biology Reports, 2024)

Single-cell transcriptome analysis of the mouse lungs during the injury and recovery periods after lipopolysaccharide administration - Hou-Ping Wang; Jian He; Jian-Rong He; Dan-Dan Li; He Huang; Bing Chen (Inflammation Research, 2024)

Active tectonic deformation and its seismic–geological significance of boundary faults of the Daxing Uplift and Langgu–Dachang Depression, Beijing Plain, China - Rong-Ying Zheng; Zhong-Yuan Yu; Bai-Xu Chen; Lu-Wei Li; Yi-Cheng Wang (Applied Geophysics, 2024)

Methylobacterium nigriterrae sp. nov., isolated from black soil - Le-Bin Chen; Yu-Ting OuYang; Lan Liu; Pin-Jiao Jin; Rong-Rong Huang; Wen-Yi Pan; Ying Wang; Jia-Ying Xing; Ting-Ting She; Jian-Yu Jiao; Shuang Wang; Wen-Jun Li (Antonie van Leeuwenhoek, 2024)

White matter lesions contribute to motor and non-motor disorders in Parkinson’s disease: a critical review - Yue-Qi Jiang; Qiu-Zhu Chen; Yang Yang; Cai-Xia Zang; Jing-Wei Ma; Jin-Rong Wang; Yi-Rong Dong; Ning Zhou; Xing Yang; Fang-Fang Li; Xiu-Qi Bao; Dan Zhang (GeroScience, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Performance of a novel annular electric field membrane bioreactor and its membrane fouling control in treating catering wastewater - Rong Zhang; Mengqian Li; Huan Ma; Yanyan Wang; Beiyu Xin; Jifeng Guo (Chemosphere, 2024)

Exploring the variations in molecular characteristics of dissolved organic matter driven by aquaculture types - Li-Ping Li; Xin-Yi Jiao; Shuang Peng; Dong-Bin Wei; Yan-Chao Jin; Cai-Shan Wang; Ding Pan; Peng Liu; Xue-Rong Wang; Yu-Ping Tang; Dong Ren; Xin-Hui Liu (Water Research, 2024)

Unraveling phytoremediation mechanisms of the common reed (Phragmites australis) suspension cells towards ciprofloxacin: Xenobiotic transformation and metabolic reprogramming - Bin Wang; Hang Xu; Yu Liu; Kaiping Zhou; Xinyu Li; Deyang Kong; Jinmei Chen; Yujie He; Rong Ji (Water Research, 2024)

Study on Translational toxicology of Senna obtusifolia aqueous extract - Xin Guo; Liping Gong; Chong Guo; Taotao Cai; Nana Huang; Xianhui Shen; Lisong Sheng; Rongrong Li; Yanqing Wang; Xinmei Zhao; Wenhe Guo; Rong Sun (Toxicon, 2024)

Emission, distribution and formation characteristics of polybrominated dibenzo-p-dioxins and dibenzofurans during co-disposal of hexabromocyclododecane-containing waste in cement kiln - Jian Wang; Bingcheng Lin; Xiao Wang; Guorui Liu; Rong Jin; Jukun Xiong; Jianping Guo; Yinming Li; Minghui Zheng (Science of The Total Environment, 2024)

Effects of 2,4,6-Trichloroanisole on the morphological development and motility of zebrafish - Yanxia Zuo; Fang Zhou; Rong Huang; Zhihui Jia; Juhong Xie; Guangxin Wang; Shuzhao Jia; Yongming Li; Manyi Wang; Lanjie Liao; Feng Ge; Yaping Wang (Science of The Total Environment, 2024)

PM2.5 constituents associated with mortality and kidney failure in childhood-onset lupus nephritis: A 19-year cohort study - Guohua He; Yaqi Wang; Cheng Cheng; Jianhui Guo; Zhilang Lin; Ziyun Liang; Bei Jin; Liyuan Tao; Liping Rong; Lizhi Chen; Tianxin Lin; Yining Hua; et al. (Science of The Total Environment, 2024)

Improved global estimation of seasonal variations in C3 photosynthetic capacity based on eco-evolutionary optimality hypotheses and remote sensing - Yihong Liu; Jing M. Chen; Mingzhu Xu; Rong Wang; Weiliang Fan; Wenyu Li; Lucas Kammer; Colin Prentice; Trevor F. Keenan; Nicholas G. Smith (Remote Sensing of Environment, 2024)

A joint-threshold Filippov model describing the effect of intermittent androgen-deprivation therapy in controlling prostate cancer - Aili Wang; Rong Yan; Haixia Li; Xiaodan Sun; Weike Zhou; Stacey R. Smith (Mathematical Biosciences, 2024)

Microplastics from polyvinyl chloride agricultural plastic films do not change nitrogenous gas emission but enhance denitrification potential - Xiaofang Ma; Zhijun Wei; Xiaomin Wang; Chenglin Li; Xueying Feng; Jun Shan; Xiaoyuan Yan; Rong Ji (Journal of Hazardous Materials, 2024)

Degradation characteristics and effect mechanisms of estrogens during aerobic composting of chicken manure based on the orthogonal test - Ziwei Liang; Junhao Wu; De-Chun He; Yan Li; Yan-Qiu Liang; Jia-Wu Hu; Meng-Yao Zou; Jian-Feng Ning; Wang-Rong Liu (Journal of Environmental Management, 2024)

Improving curcumin bioavailability: Targeted delivery of curcumin and loading systems in intestinal inflammation - Junyi Zhao; Wei Jia; Rong Zhang; Xin Wang; Li Zhang (Food Research International, 2024)

Investigation of isomerization and oxidation of astaxanthin in ready-to-eat Litopenaeus vannamei during accelerated storage - Na Li; Xin Fan; Yefan Wang; Kexin Zhang; Rong Liu; Yunpeng Xu; Zhifeng Tan; Wensi Xu; Dayong Zhou; Deyang Li (Food Research International, 2024)

Metagenomic analysis unveiled the response of microbial community and antimicrobial resistome in natural water body to duck farm sewage - Chang Fang; Kai-di Liu; Feng-jie Tian; Jin-ying Li; Si-jie Li; Rong-min Zhang; Jian Sun; Liang-xing Fang; Hao Ren; Min-ge Wang; Xiao-ping Liao (Environmental Pollution, 2024)

Fate and drivers of mariculture-derived microplastics from ponds to mangrove forests - Zhen Zhao; Yihua Wei; Yijin Wang; Gen Peng; Eddy Y. Zeng; Kefu Yu; Xiang-Rong Xu; Ruilong Li (Environmental Pollution, 2024)

Heterostructured GCN Nanosheets/ZnO nanoflowers for enhanced TMO loading: From high-performance three electrode systems to printed flexible asymmetric supercapacitors - Xuhao Wang; Fenglin Sun; Fuhao Jiang; Binxuan Diao; Rong Wang; Hongjiang Li; Sang Woo Joo; Rong Li; Se Hyun Kim; Chenhao Cong; Xinlin Li (Chemical Engineering Journal, 2024)

A surfactant-mediated dynamic protection strategy for 100% waterborne fabrication of durable superhydrophobic coatings - Rong-Gang Zhang; Rui Feng; Fang Wang; Hang-Lin Li; Ren-Yi Sun; Hui-Hui Gao; Chun-Bo Li; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2024)

High-performance hydrogel membranes with superior environmental stability for harvesting osmotic energy - Caiqin Wu; Rong Wu; Huan Zeng; Chenling Yao; Jialing Zhou; Guilong Li; Jian Wang (Chemical Engineering Journal, 2024)

Simple theranostics nanoagent for precision suppression of tumor growth and metastasis: A traditional fermented product having a novel functional breakthrough - Pengmin Liu; Rong Dai; Juan Li; Lin Chen; Qi Liu; Yuhang Wang; Shichao Meng; Binyue Zhang; Jinxuan Li; Weiwei Kang; Ziliang Zheng; Ruiping Zhang (Chemical Engineering Journal, 2024)

Durable PVDF photocatalytic membranes with TiO2@PDA incorporated into/onto for dye degradation under visible-light - Thi My Hanh Le; Yi-Ning Wang; Can Li; Rong Wang; Sermpong Sairiam (Chemical Engineering Journal, 2024)

Enhanced photocatalytic hydrogen evolution via yolk–heteroshell TiO2@TiO2/SiO2 nanoreactor with confined Pt nanoparticles - Haimei Liu; Min Shi; Rong Yang; Ye Wang; Haiyan li; Qiying Su; Tao Wang; Sheng Wang (Chemical Engineering Journal, 2024)

Preparation of super toughened flame-retardant polylactic acid with an in situ hyperbranched structure by reactive blending with a phosphorus-containing copolyester and hexamethylene glycidyl cyclotriphosphazene - Guozhang Gu; Huaiyang Cai; Yutao Wang; Chen Tang; Guoxiang Zou; Jinchun Li; Rong Yang (Chemical Engineering Journal, 2024)

Controlled assembly and synthesis of oxygen-deficient W18O49 films based on solvent molecular strategy for electrochromic energy storage smart windows - Xiaohui Sun; Wei Wu; Nana Liu; Peng Li; Xueying Zhao; Zhaozhu Qu; Kunming Zhao; Bo Wang; Xianhui Rong; Xuyang Zhang; Guohua Wu; Xiangwei Wang (Chemical Engineering Journal, 2024)

Fabrication of graphene oxide/ammonium molybdophosphate composite membrane for decontamination of cesium ions from seawater - Xiao-Yi Tang; Zi-Jie Li; Lin Wang; Peng-Cheng Zhang; Kong-Qiu Hu; Li-Rong Zheng; Zhi-Hui Zhang; Li-Yong Yuan; Wang-Suo Wu; Wei-Qun Shi (Chemical Engineering Journal, 2024)

Bioactives from biomass: Treasure for future potent antimicrobial applications - Weicheng Chen; Peng Zhang; Yucui Ding; Xiaobin Xie; Jianlong Fu; Rong Zhao; Yihan Xiao; Miodrag J. Lukic; Bin Li; Weishan Wang; Song Chen (Chemical Engineering Journal, 2024)

Effects of microplastics on potato verticillium wilt and microbial community of rhizosphere soil - Naqi Cui; Hongwu Liang; Weisong Zhao; Mingzhu Zhao; Yu Wang; Qinggang Guo; Zihui Rong; Shezeng Li; Ping Ma (Applied Soil Ecology, 2024)

A novel hollow flower shaped Cu9S8 antibacterial agent for removing sulfonamide in water environment: effects of composite with magnetic biochar, differential adsorption, and mechanism study - Rui-peng Li; Zheng-rong Hu; Xing Wang; Jun Chen; Qing-qing Liu; Ying Zhao; Zhong-bao Zhao; Xu-lin Lu; Zhi-wei Zhang (Environmental Science and Pollution Research, 2024)

Early detection of fungal infection in citrus using biospeckle imaging - Si Yang; Chenxi Li; Xinyu Li; Jingying Jiang; Yansong Zhao; Xiaoli Wang; Wenliang Chen; Rong Liu; Kexin Xu (Computers and Electronics in Agriculture, 2024)

Recent research and development of individual precision cooling systems for dairy cows – A review - Wenqi Zhang; Ruimin Yang; Christopher Y. Choi; Li Rong; Guoqiang Zhang; Kaiying Wang; Xiaoshuai Wang (Computers and Electronics in Agriculture, 2024)

Precipitation contributes to alleviating pollution of rubber-derived chemicals in receiving watersheds: Combining confluent stormwater runoff from different functional areas - Yue-Hong Liu; Yu-Xian Mei; Jing-Yi Wang; Shan-Shan Chen; Jia-Li Chen; Nan Li; Wang-Rong Liu; Jian-Liang Zhao; Qian-Qian Zhang; Guang-Guo Ying (Water Research, 2024)

Effects of microplastics derived from biodegradable mulch film on different plant species growth and soil properties - Rong Liang; Chi Zhang; Ruifang Zhang; Qingyun Li; Hongquan Liu; Xin-Xin Wang (Science of The Total Environment, 2024)

Effects of socioeconomic status and regional inequality on the association between PM2.5 and its components and cardiometabolic multimorbidity: A multicenter population-based survey in eastern China - Zhiqian Cui; Xinxu Yi; Yuxin Huang; Ming Li; Zichen Zhang; Lingmei Kuang; Rong Song; Jintao Liu; Rubing Pan; Weizhuo Yi; Xiaoyu Jin; Jian Song; et al. (Science of The Total Environment, 2024)

Late Holocene rapid paleoenvironmental changes and anthropogenic impacts in central Yunnan, southwest China - Zhikai Xue; Weiwei Sun; Beibei Shen; Rong Wang; Chunhai Li; Enlou Zhang (Quaternary International, 2024)

Environmental high temperature affects pre-implantation embryo development by impairing the DNA repair ability - Si-Jing Qu; Shi-Yong Zhu; En-Yan Wang; Xin-Lei Yan; Rong-Feng Cao; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2024)

Combating coal-burning-borne endemic arsenism in Shaanxi Province, Northwest China: The impact of high-arsenic coal ban, improved cook-stoves, and health education - Yujie Ning; Chaowei Wang; Shujin Li; Sijie Chen; Feiyu Zhang; Rong Zhou; Yuequan Yuan; Xi Lv; Yifan Wu; Yu Zhang; Zhongxue Fan; Xiaoqian Li; et al. (Journal of Hazardous Materials, 2024)

Construction of oxygen-doped g-C3N4/BiOCl (S-scheme) heterojunction: Efficient degradation of tetracycline in wastewater - Yuan Wei; Yu-Bing Liu; Chao Liu; Xin Li; Guang-Hong Zhao; Rong-Hui Liu; Hong-Yu Wang; Yan-Yan Jiang; Yu-Lan Zhang; Yu-Hui Gao; Gao-Feng Shi; Guo-Ying Wang (Journal of Environmental Chemical Engineering, 2024)

Enhanced hydrate formation at the liquid CO2-brine interface with shear flow for solid CO2 sequestration - Ming-Long Wang; Yi-Fei Sun; Wei-Xin Pang; Qing-Ping Li; Ting Huang; Hong-Nan Chen; Ming Wang; Jin-Rong Zhong; Liang-Liang Ren; Dan Rao; Bei Liu; Chang-Yu Sun; et al. (Gas Science and Engineering, 2024)

Gum arabic coating alleviates chilling injury of cold-stored peach by regulating reactive oxygen species, phenolic, and sugar metabolism - Zengyu Gan; Yupei Zhang; Ziteng Jin; Yongjie Wang; Jiali Li; Caining Yang; Qing Cao; Jinyin Chen; Zhenbang Rong; Xuming Lu; Suqin Guo (Food Chemistry, 2024)

The impacts of cold plasma on the taste and odor formation of dried silver carp products - Yueying Zhai; Aonan Luan; Zhimeng Yang; Zhixing Rong; Yongle Liu; Faxiang Wang; Xianghong Li (Food Chemistry, 2024)

Effects of soy protein on alleviating iron deficiency anemia in suckling rats with different iron supplements - Mengxiao Hu; Jun Zhou; Lili Qiu; Rui Song; Xiyu Qin; Zidi Tan; Wei Wang; Rong Liu; Yun Li; Yingyi Mao; Xiang Li; Fei Li; et al. (Food Bioscience, 2024)

Development of easy-to-swallow and lipid-enhanced 3D printed surimi based on high internal phase emulsions - Wei Liang; Yuhang Wang; Chuan Li; Pengkai Wang; Jianhua Rong; Ru Liu; Shanbai Xiong; Yang Hu (Food Hydrocolloids, 2024)

Enhanced solar-driven steam generation and water purification using 3D arch solar evaporators - Yong-Gang Wu; Chao-Hua Xue; Xiao-Jing Guo; Meng-Chen Huang; Hui-Di Wang; Chao-Qun Ma; Li Wan; Shi-Qiang Lv; Wen-Min Zhang; Rong-Rong Gao (Desalination, 2024)

Successful subduction of oceanic plate after failed attempts in the Late Archean: Petrological and geochemical constraints - Xi Wang; Rong-Feng Ge; Yong-Fei Zheng; Wen-Bin Zhu; San-Zhong Li; Rong-Song Tian; Yue Wang; Yi-Wei Rong (Earth and Planetary Science Letters, 2024)

Constructing ultralow-loading Cu single atoms/Fe2O3 particles on Nb2C MXenes for efficient utilization of atomic H to boost electrochemical debromination - Fangxian Wang; Junwei Yang; Shihao Li; Junwen Liang; Yuwei Wang; Rong Du; Bo Zhou; Qiong Liu; Changping Li (Chemical Engineering Journal, 2024)

Mitigating nitrite inhibition in Klebsiella strain denitrification: Stimulating endogenous driving force with microscale zero-valent iron - Wen-ying Cao; Kuang-di Xu; Su Zhang; Si-jia Li; Yi-cheng Yuan; Jing-xuan Lu; Lei Yu; Shao-hua Zhou; Jun-ting Gan; Quan Wang; Rong-ping Chen; Ke Yin (Chemical Engineering Journal, 2024)

Low oxygen adsorption energy barrier architectures to facilitate microenvironmental photocatalytic disinfection in Wei River - Lenan Yao; Yunyan Bai; Li Ding; Yayun Hu; Zuwang Zhang; Yajie Zhang; Rui Chen; Haijiao Xie; Jianlong Wang; Rong Wang (Chemical Engineering Journal, 2024)

Synergistic metabolism intervention and immune activation for antitumor therapy by biomineralized lactate oxidase - Yuxuan Ge; Zixin Wang; Yujia Lu; Fan Rong; Bin Hao; Zhao Li; Junsheng Chen; Yin Wang (Chemical Engineering Journal, 2024)

Developing Estimation Equations for the Cerchar Abrasivity Index of Rocks Applicable to TBM Tunnels - Lei She; Yan-long Li; She-rong Zhang; Chao Wang; Sun-wen He; Yu-jie Wang; Ming-ming He; Sheng-le Wang (Rock Mechanics and Rock Engineering, 2024)

Influenza A Virus PB1-F2 Induces Affective Disorder by Interfering Synaptic Plasticity in Hippocampal Dentate Gyrus - Saiying Wang; Haijun Zhang; Rui Liu; Peijun Han; Qi Yang; Caiyan Cheng; Yue Chen; Zheng Rong; Chang Su; Fei Li; Gaofei Wei; Minggao Zhao; et al. (Molecular Neurobiology, 2024)

Label-Free Detection of Programmed Death-Ligand 1 for Prognosis Using a Truncated Aptamer and SYBR Green I - Ling Li; Zheng-Ling Li; Wei Wang; Xin-Xin Long; Ping Liu; Guo-Tian Wang; Shi-Qing Sun; Rong-Lian Du (Journal of Fluorescence, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Role of NF-κB signaling pathway in H2O2-induced oxidative stress of hiPSCs - Jian Qin; Jie Yang; Jun Li; Dipeng Zhao; Jie An; Zhuhui Zhai; Hejie Wang; Junling Li; Minmin Dou; Rong Du (In Vitro Cellular & Developmental Biology - Animal, 2024)

Investigating protistan predators and bacteria within soil microbiomes in agricultural ecosystems under organic and chemical fertilizer applications - Chen Liu; Zeyuan Zhou; Shuo Sun; Qi Zhang; Shiqi Sun; Xinnan Hang; Mohammadhossein Ravanbakhsh; Zhong Wei; Rong Li; Shimei Wang; Wu Xiong; George A. Kowalchuk; et al. (Biology and Fertility of Soils, 2024)
Organic farming can enhance biodiversity and soil health and is a sustainable alternative to conventional farming. Yet, soil protists especially protistan predators, have received inadequate attention, and their contributions to the sustainability of organic farming remained underexplored. In this study, we examined soil microbial communities from 379 samples, including both organic and chemically fertilized soils from China. Our findings revealed higher bacterial diversity and increases in plant-beneficial bacteria in organically farmed soils. Notably, organic farming systems facilitated dynamic predator-prey interactions, which may be disrupted by the application of chemical fertilizers. Additionally, organic farming enriched protistan predators, enhancing the relative abundance of functional PGPR, thus improving soil health. We further conducted a case study highlighting the critical role of organic matter in sustaining protistan predator populations and their interactions with bacteria. We propose the crucial contributions of organic inputs for supporting protistan predators and the interplay of predator-prey, ultimately enhancing soil functions and promoting agricultural sustainability.

Dual colorimetric platforms for direct detection of glyphosate based on Os-Rh nanozyme with peroxidase-like activity - Yingying Zhong; Junsong Yang; Wanying Wu; Haoyang Chen; Shuwei Li; Ziying Zhang; Shicheng Rong; Hongwu Wang (Analytica Chimica Acta, 2024)

Glutamine deprivation in glioblastoma stem cells triggers autophagic SIRT3 degradation to epigenetically restrict CD133 expression and stemness - Zhengcao Xing; Xianguo Jiang; Yalan Chen; Tiange Wang; Xiaohe Li; Xiangyun Wei; Qiuju Fan; Jie Yang; Hongmei Wu; Jinke Cheng; Rong Cai (Apoptosis, 2024)

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

MicroRNA dynamics in irisin-mediated signaling pathways within adipose tissue - Ming-Yun Ho; Kai-Pin Chiu; Ming-Lung Tsai; Jih-Kai Yeh; Yi-Chun Huang; Yan-Rong Li; Horng-Dar Wang; I-Chang Hsieh; Ming-Shien Wen; Chao-Yung Wang (Journal of Biosciences, 2024)

Nervonic acid and its sphingolipids: Biological functions and potential food applications - Nghi Van Phung; Fei Rong; Wan Yue Xia; Yong Fan; Xian Yu Li; Shi An Wang; Fu Li Li (Critical Reviews in Food Science and Nutrition, 2024)

Cloning and functional identification of anthocyanin synthesis-regulating transcription factor AaMYB4 in Aeonium arboreum Webb & Berthel ‘Halloween’ - Rong Zhao; Su-Hua Li; Hao-Zhang Han; Li-Hua Zhang; Fang Wang; Nan Zhang (Brazilian Journal of Botany, 2024)

Sequential Two-Mode Fusion Underwater Single-Photon Lidar Imaging Algorithm - Tian Rong; Yuhang Wang; Qiguang Zhu; Chenxu Wang; Yanchao Zhang; Jianfeng Li; Zhiquan Zhou; Qinghua Luo (Journal of Marine Science and Engineering, 2024)
Aiming at the demand for long-range and high-resolution imaging detection of small targets such as submerged submarine markers in shallow coastal waters, research on single-photon lidar imaging technology is carried out. This paper reports the sequential two-mode fusion imaging algorithm, which has a strong information extraction capability and can reconstruct scene target depth and reflection intensity images from complex signal photon counts. The algorithm consists of four steps: data preprocessing, extremely large group value estimation, noise sieving, and total variation smoothing constraints to image the target with high quality. Simulation and test results show that the imaging performance and imaging characteristics of the method are better than the current high-performance first-photon group imaging algorithm, indicating that the method has a great advantage in sparse photon counting imaging, and the method proposed in this paper constructs a clear depth and reflectance intensity image of the target scene, even in the 50,828 Lux ambient strong light and strong interference, the 0.1 Lux low-light environment, or the underwater high-attenuation environment.

CXCR3 participates in asymmetric division of mouse oocytes by modulating actin dynamics - Wei-jian Li; Rong-yang Li; Da-yu Wang; Ming Shen; Hong-lin Liu (Theriogenology, 2024)

Preliminary assessments of carbon release driven by Late Pleistocene Arctic ice sheets - Liming Ye; Xiaoguo Yu; Yeping Bian; Weijia Fan; Zhongqiang Ji; Sai Song; Ziyin Wu; Qian Ge; Dong Xu; Weiyan Zhang; Haiyan Jin; Xiaohu Li; et al. (Quaternary Science Reviews, 2024)

A pooled mycoviral resource in a strain of Rhizoctonia solani are regulators of fungal virulence - Ya Rong Wang; Jia En Su; Zhi Juan Yang; Jie Zhong; Xiao Gang Li; Yi Chen; Jun Zi Zhu (Pesticide Biochemistry and Physiology, 2024)

Genetic variation in a heat shock transcription factor modulates cold tolerance in maize - Lei Gao; Lingling Pan; Yiting Shi; Rong Zeng; Minze Li; Zhuoyang Li; Xuan Zhang; Xiaoming Zhao; Xinru Gong; Wei Huang; Xiaohong Yang; Jinsheng Lai; et al. (Molecular Plant, 2024)

Trade-offs of reproductive growth and Cd remobilization regulated Cd accumulation in wheat grains (Triticum aestivum L.) - Ying Wang; Pei-Pei Gao; Yu-Meng Shang; Rong-Rong Jia; Yu-Cheng Wang; Xiang-Yu Li; Li-Ping Geng; Yong Zhao; Joshua Walrath; Wen-Ju Liu (Journal of Hazardous Materials, 2024)

p‑Phenylenediamine antioxidants in PM2.5: New markers for traffic in positive matrix factorization source apportionment - Nan Jiang; Xuexin Hao; Zichen Wang; Minzhen Li; Dong Zhang; Rong Cao; Ruiqin Zhang; Haijun Zhang; Jiping Chen; Ningbo Geng (Journal of Hazardous Materials, 2024)

Biofilm growth characteristic and footprint identification in gravity-driven ceramic membrane bioreactor with electro-coagulation under extreme conditions for roofing rainwater purification - Wei Song; Rong Ma; Zhenhao Liang; Jiawan Li; Jiahao Dong; Xing Du; Zhihong Wang; Xianhui Li (Journal of Environmental Management, 2024)

Corrigendum to “Distribution of organophosphorus pesticides and its potential connection with probiotics in sediments of a shallow freshwater lake” [Journal of Contaminant Hydrology 261 (2024) 104306] - Yanping Hu; Rong Xiao; Yaping Wang; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Javiera Manquian; Wenbin Pan (Journal of Contaminant Hydrology, 2024)

Enzymatically green-produced bacterial cellulose nanoparticle-stabilized Pickering emulsion for enhancing anthocyanin colorimetric performance of versatile films - Shiqi Li; Rong Liu; Jiale Zhao; Shuo Zhang; Xuerong Hu; Xingnan Wang; Zhenpeng Gao; Yahong Yuan; Tianli Yue; Rui Cai; Zhouli Wang (Food Chemistry, 2024)

Accumulation and ecological risk assessment of diazinon in surface sediments of Baiyangdian lake and its potential impact on probiotics and pathogens - Yaping Wang; Rong Xiao; Yanping Hu; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Wenbin Pan (Environmental Pollution, 2024)

Two-stage exhumation, uplift, and basinward propagation of the Tian Shan during the late Cenozoic - Yutong Jiang; Honghua Lu; Rong Yang; Lichen Pang; Ruohong Jiao; Ying Wang; Jianzhang Pang; Youli Li (Earth-Science Reviews, 2024)

Scalable thermochromic superhydrophobic collagen fiber-based wearable materials for all-weather self-adaptive radiative cooling and solar heating - Meng-Chen Huang; Chao-Hua Xue; Zhongxue Bai; Hui-Di Wang; Chao-Qun Ma; Yong-Gang Wu; Li Wan; Long Xie; Shi-Qiang Lv; Rong-Rong Gao; Wen-Min Zhang; Jun Cheng; et al. (Chemical Engineering Journal, 2024)

Albumin tailoring molecular rotation and electrophilicity of a GSH-depleting radiosensitizer for potentiating ferroptosis-mediated radioimmunotherapy - Mingquan Gao; Xie Huang; Zifei Wu; Weidong Xiao; Zaizhi Du; Banghui Mo; Chuan Wu; Haiyan Xing; Weidong Wang; Rong Li; Shenglin Luo (Chemical Engineering Journal, 2024)

TBC1D1 is an energy-responsive polarization regulator of macrophages via governing ROS production in obesity - Qi Wang; Ping Rong; Wen Zhang; Xinyu Yang; Liang Chen; Ye Cao; Minjun Liu; Weikuan Feng; Qian Ouyang; Qiaoli Chen; Hailong Li; Hui Liang; et al. (Science China Life Sciences, 2024)

Argon non-thermal plasma treatment promotes the development of rice (Oryza sativa L.) in saline alkali environments - Kai Liu; Yan-Jiang Feng; Jun-Xiang Guo; Gui-Ling Wang; Li-Li Shan; Shi-Wei Gao; Qing Liu; Hu-Nan Sun; Xi-Yu Li; Xing-Rong Sun; Jing-Yang Bian; Taeho Kwon (Protoplasma, 2024)

The romantic history of signaling pathway discovery in cell death: an updated review - Lei-Yun Wang; Xing-Jian Liu; Qiu-Qi Li; Ying Zhu; Hui-Li Ren; Jia-Nan Song; Jun Zeng; Jie Mei; Hui-Xiang Tian; Ding-Chao Rong; Shao-Hui Zhang (Molecular and Cellular Biochemistry, 2024)

Soil Organic Matter and Amorphous Oxides Determine the Surface Electrochemical Properties of Purple Soil Under Long-Term Inorganic and Organic Fertilization - Jun Xie; Rong Huang; Dongxun Wu; Wencai Dai; Zhengxin Deng; Yue Li; Xiaojun Shi; Yueqiang Zhang; Zifang Wang; Ming Gao (Journal of Soil Science and Plant Nutrition, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Streptococcus taoyuanensis sp. nov., a Novel Species Isolated from a Patient with Bacteremia - Chien-Yu Lee; Chin-Kan Chan; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Jia-rong Zhang; Hong-yu Chen; Li-Ting Wang (Current Microbiology, 2024)

Copper-ion-complexed palygorskite as a novel nanozyme with enhanced peroxidase-like activity for sensitive colorimetric sensing - Ping Chen; Hui Zhong; Xiao-rong Li; Tingting Zhang; Xiang Wang; Fang Hu; Yubo Yan; Jiaxing Xu; Meisheng Li (Applied Clay Science, 2024)

Assessment of the hormesis effect and toxic damage of short-term low-dose aflatoxin B1 in grass carp (Ctenopharyngodon idellus) - Jin-long Li; Jia-rong Guo; Pei Wang; Jun-zhi Zhang; Zhi-gang He; Jin-long Wang; Yi Hu (Frontiers in Marine Science, 2024)
The present study was conducted to evaluate the hormesis and toxicity of short-term low-dose aflatoxin B1 in grass carp ( Ctenopharyngodon idellus ). Triplicate isonitrogenous and isocaloric aflatoxin B1 diets—CD (control, 0 ug/kg), D1 (20 ug/kg), and D2 (500 ug/kg)—were prepared and fed to grass carp with an initial mean body weight of (15.2 ± 0.1) g for 56 days. The results showed that the weight gain rate and specific growth rate of grass carp fed diet D2 were significantly higher, and the feed coefficient and crude fat content of the whole body were significantly lower ( P < 0.05) compared with those fed diet CD. Serum superoxide dismutase content of grass carp fed D1 diet increased significantly ( P < 0.05) with an increasing dose of aflatoxin B1, but when the dose reached 500 ug/kg (D2), serum superoxide dismutase, complement C3, and immunoglobulin M of grass carp decreased significantly ( P < 0.05), while malondialdehyde increased significantly ( P < 0.05). After short-term feeding of aflatoxin B1-containing diets (D1 and D2), liver body index, visceral body index, serum total cholesterol, triglyceride, and urea nitrogen content of grass carp increased significantly ( P < 0.05), total bile acid secretion decreased significantly ( P < 0.05), and structural damages such as increase in vacuoles, organizational structure loosening, and nucleus translocation were observed in the liver. Meanwhile, liver function indexes such as serum alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase increased significantly with the increase of aflatoxin B1 dose ( P < 0.05). In addition, the height of intestinal villi, crypt depth, villus–crypt ratio, and tubular cell number, as well as the content of trypsin and lipase activities in the intestine of grass carp in the D2 group, were significantly higher than those in the CD group ( P < 0.05). In conclusion, after a short-term intake of low doses of aflatoxin B1 (≤500 ug/kg), the toxicological damage of aflatoxin B1 was pronounced, although it produced a certain degree of hormesis on the growth performance and intestinal structure and function of grass carp. At a dose of 20 ug/kg, the non-specific immune system and liver structure and function of grass carp showed obvious toxic damage.

Application of luminescent Photobacterium Phosphoreum T3 for the detection of zearalenone and estimating the efficiency of their enzymatic degradation - Shu-Rong Chen; Li-Hong Chen; Li Pan; Bin Wang (Food Additives & Contaminants: Part A, 2024)

Corrigendum to “Pathogen profile of Baiyangdian Lake sediments using metagenomic analysis and their correlation with environmental factors” [Sci. Total Environ. 913 (2024) 169628] - Rong Xiao; Yanping Hu; Yaping Wang; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Jacquelinne J. Acuña; Wenbin Pan (Science of The Total Environment, 2024)

Molecular insights into the functional analysis of P450 CYP321A7 gene in the involvement of detoxification of lambda-cyhalothrin in Spodoptera frugiperda - Wan-Ting Li; Jia-Yu Lin; Jia-Jie Liu; Muhammad Hafeez; Shi-Wen Deng; Hong-Yu Chen; Rong-Jie Ren; Muhammad Shoaib Rana; Rui-Long Wang (Pesticide Biochemistry and Physiology, 2024)

Temporal variations in dissolved organic matter properties in a eutrophic lake under water dilution and aquatic plant litter decomposition: A simulated microcosm study revealing the environmental and microbial driving factors - Rong Wu; Haoyu Wang; Wei Li; Xiaowan Chen; Qichao Zhou; Junjun Chang (Journal of Water Process Engineering, 2024)

Spatial distribution of bioaerosols and evaluation of four ventilation method on controlling their diffusion in a typical enhanced biosafety level 2 laboratory - Zhijian Liu; Yongxin Wang; Chuan Jiang; Junzhou He; Rui Rong; Shiyue Li; Zhenyu Liang (Journal of Hazardous Materials, 2024)

In-situ electric swing adsorption enabling superior water vapor capture of salt-based carbon fibers - Rong Zhu; Yaowei Huang; Qiongfen Yu; Ming Li; Yunfeng Wang; Ying Zhang (Journal of Environmental Chemical Engineering, 2024)

Development of an ELISA method to determine adulterated cow milk in camel milk - Shi-Xin Chi; Bo-Hao Liu; Bing Zhang; Bao-Rong Wang; Jie Zhou; Ling Li; Ying-Hua Zhang; Zhi-shen Mu (International Dairy Journal, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

A two-step method of cyclolinopeptide (linusorb) preparation from flaxseed cake via dry-screening - Zi-zhe Cai; Chen-xin Xu; Zi-liang Song; Jun-le Li; Ning Zhang; Jian-hao Zhao; Yee-Ying Lee; Martin J.T. Reaney; Fu-rong Huang; Yong Wang (Food Chemistry, 2024)

Superior energy storage properties with prominent thermal stability in lead-free KNN-based ceramics through multi-component optimization strategy - Qifan Chen; Hao Chen; Dong Wang; Tingting Gao; Qinyu Li; Rong Lang; Zhi Tan; Jie Xing; Jianguo Zhu (Chemical Engineering Journal, 2024)

Utilization of tofu wastewater and Nannochloropsis oceanica for eutrophication mitigation and eicosapentaenoic acid valorization: Advancing carbon neutrality and resource recycling - Yuqin Li; Xing Meng; Zhenyao Wang; Xin Lin; Yuan Xu; Jinhua Mou; Rong Zhou; Yufang Tang; Carol Sze Ki Lin; Xuan Li (Chemical Engineering Journal, 2024)

Regulatory mechanisms of biochar alleviating ammonia inhibition to methanogenesis during long-term operation of anaerobic membrane bioreactor treating swine wastewater - Bo Zhang; Gaojun Wang; Xiang Zhang; Peng Fu; Lu Chen; Yizhi Chen; Qian Li; Rong Chen (Chemical Engineering Journal, 2024)

Molecular insights into the interactions of theaflavin and epicatechin with different lipid bilayer membranes by molecular dynamics simulation - Rong-zu Nie; Huo-min Luo; Jing-yu Chen; Li-heng Sun; Zi-bo Wang; Zhen-ping Zhang; Ya-ru Bao (Chemistry and Physics of Lipids, 2024)

Adenylate kinase phosphate energy shuttle underlies energetic communication in flagellar axonemes - Huan Wu; Yanman Zhang; Yuqian Li; Shuya Sun; Jintao Zhang; Qingsong Xie; Yue Dong; Shushu Zhou; Xuan Sha; Kuokuo Li; Jinyi Chen; Xin Zhang; et al. (Science China Life Sciences, 2024)

Empagliflozin attenuates doxorubicin-impaired cardiac contractility by suppressing reactive oxygen species in isolated myocytes - Rong Lin; Xiaodong Peng; Yukun Li; Xuesi Wang; Xinmeng Liu; Xingze Jia; Chengjun Zhang; Nian Liu; Jianzeng Dong (Molecular and Cellular Biochemistry, 2024)

Investigation of New Integrated Drought Monitoring Model Taking into Account the Effects of Climate Anomalies - Lei Zhou; Wenliang Wang; Congcong He; Siyu Wang; Yalan Li; Rong Tian; Cheng Du (Journal of the Indian Society of Remote Sensing, 2024)

Identification of the Galactinol Synthase (GolS) Family in Medicago truncatula and Expression Analysis Under Abiotic Stress and Phytohormone Treatment - Hua Li; Ying Di Gao; Li Qing Kang; Hong Yang Yu; Li Ming Zeng; Yi Hua Wang; Rong Rong Chen; Jian Bo Song (Journal of Plant Growth Regulation, 2024)

Mass cytometry revealed the circulating immune cell landscape across different Suzuki stages of Moyamoya disease - Chenglong Liu; Peicong Ge; Bojian Zhang; Liujia Chan; Yuheng Pang; Chuming Tao; Junsheng Li; Qiheng He; Wei Liu; Siqi Mou; Zhiyao Zheng; Zhikang Zhao; et al. (Immunologic Research, 2024)
Moyamoya disease (MMD) is a cerebrovascular disorder marked by progressive arterial narrowing, categorized into six stages known as Suzuki stages based on angiographic features. Growing evidence indicates a pivotal role of systemic immune and inflammatory responses in the initiation and advancement of MMD. This study employs high-dimensional mass cytometry to reveal the immunophenotypic characteristics of peripheral blood immune cells (PBMCs) at various Suzuki stages, offering insights into the progression of MMD. PBMC samples from eight patients with early-stage MMD (Suzuki stages II and III) and eight patients with later-stage MMD (Suzuki stages IV, V, and VI) were analyzed using high-dimensional mass cytometry to evaluate the frequency and phenotype of immune cell subtypes. We identified 15 cell clusters and found that the immunological features of early-stage MMD and later-stage MMD are composed of cluster variations. In this study, we confirmed that, compared to later-stage MMD, the early-stage MMD group exhibits an increase in non-classical monocytes. As the Suzuki stage level increases, the proportions of plasmacytoid DCs and monocyte-derived DCs decrease. Furthermore, T cells, monocytes, DCs, and PMN-MDSCs in the early-stage MMD group show activation of the canonical NF-κB signaling pathway. We summarized and compared the similarities and differences between early-stage MMD patients and later-stage MMD patients. There is a potential role of circulating immune dysfunction and inflammatory responses in the onset and development of MMD.

Deubiquitinating enzyme OTUD4 stabilizes RBM47 to induce ATF3 transcription: a novel mechanism underlying the restrained malignant properties of ccRCC cells - Ziyao Li; Ye Tian; Huafeng Zong; Xuelei Wang; Dongyang Li; Adili Keranmu; Shiyong Xin; Bowen Ye; Rong Bai; Weihua Chen; Guosheng Yang; Lin Ye; et al. (Apoptosis, 2024)

Examining the Potential of ChatGPT on Biomedical Information Retrieval: Fact-Checking Drug-Disease Associations - Zhenxiang Gao; Lingyao Li; Siyuan Ma; Qinyong Wang; Libby Hemphill; Rong Xu (Annals of Biomedical Engineering, 2024)

Assessment of spray nozzles on water distribution on cow’s surface and efficiency of water utilization by CFD - Ruimin Yang; Christopher Y. Choi; Li Rong; Guoqiang Zhang; Xiaoshuai Wang (Computers and Electronics in Agriculture, 2024)

Genomic analysis of Clostridium perfringens type D isolates from goat farms - Hang Feng; Ke Wu; Yuan Yuan; Mingjin Fang; Juan Wang; Ruichao Li; Rong Zhang; Xinglong Wang; Dongyang Ye; Zengqi Yang (Veterinary Microbiology, 2024)

MicroRNA expression profile of chicken liver at different times after Histomonas meleagridis infection - Qiaoguang Chen; Yuming Zhang; Jie Rong; Chen Chen; Shuang Wang; Jiege Wang; Zaifan Li; Zhaofeng Hou; Dandan Liu; Jianping Tao; Jinjun Xu (Veterinary Parasitology, 2024)

Timing and Kinematics of late Cenozoic Strike-slip Faults in the Western Tibetan Plateau: New Constraints from Provenance Analysis and Detrital Thermochronology - Xiaochun Wei; Hanlin Chen; Rong Yang; Ping Wang; Shanying Li; Xuhua Shi; Jin Ge (Tectonophysics, 2024)

Toxic nonpreferred species accelerate the natural restoration of plant productivity and diversity in degraded grasslands - Xiaona Zheng; Chen Chen; Xin Dai; Le Lang; Xing Li; Jigui Chen; Rong Wang; Wenhui Cai; Ying Gao (Science of The Total Environment, 2024)

Combined effects of cadmium and sulfamethoxazole on Eisenia fetida: Insights into accumulation, subcellular partitioning, biomarkers and toxicological responses - Sheng-Nan Zhang; Yi-Tong Zhou; Jun Xia; Yu-Meng Wang; Jun-Wei Ma; Li-Kun Wang; Kashif Hayat; Shan-shan Bai; Cheng-han Li; Ming-Rong Qian; Hui Lin (Science of The Total Environment, 2024)

Preharvest spraying with L-Phenylalanine effectively delayed the degradation of chlorophyll in postharvest broccoli - Xiwang Wang; Deyun Lou; Li Li; Rong Li; Wenyi Xu; Xiaojing Wang; Yongcai Li; Yang Bi (Postharvest Biology and Technology, 2024)

Biocontrol performance of a novel Bacillus velezensis L33a on tomato gray mold and its complete genome sequence analysis - Lixinyu Sun; Yu Chen; Shiyu Liu; Xiaogang Ou; Yangyang Wang; Zhengwu Zhao; Rong Tang; Yingzhe Yan; Xinyue Zeng; Shun Feng; Tao Zhang; Zhengguo Li; et al. (Postharvest Biology and Technology, 2024)

SAD2 functions in plant pathogen Pseudomonas syringae pv tomato DC3000 defense by regulating the nuclear accumulation of MYB30 in Arabidopsis thaliana - Tiantian Shi; Yuan Zheng; Rui Wang; Sha Li; Andi Xu; Luoying Chen; Yuanhang Liu; Rong Luo; Chenchen Huang; Yinglu Sun; Jinfeng Zhao; Xiaoying Guo; et al. (Plant Science, 2024)

Efficient removal of the residual ammonium from weathered crust elution-deposited rare earth tailings by a ternary compound eluent - Xiaoju Li; Junxia Yu; Xiaodi Li; Rong Wang; Fang Zhou; Zhenyue Zhang; Chunqiao Xiao; Ruan Chi (Minerals Engineering, 2024)

Electrocatalytic nitrate removal by non-precious three-dimensional Fe/Ni foam cathode: Experimental study and mechanism verification - Xiaodan Wang; Xi Ma; Yaoyao Wu; Chuanhao Li; Rong Chen (Journal of Water Process Engineering, 2024)

Inactivation of Aeromonas hydrophila in water by dielectric barrier discharge plasma: Efficiency, mechanism, and application safety - Le Wang; Zhenfei Zhu; Pengcheng Yan; Rong Zhang; Min Zhang; Xiangyu Wang; Guangzhou Qu; Tiecheng Wang; Ronghua Li (Journal of Water Process Engineering, 2024)

In situ visualization on the mobility of mineral associated organic matter in a microfluidics-based heterogeneous soil aggregate structure - Minru Cheng; Mingang Dong; Peng Liao; Haoran Wang; Zhenqing Shi; Rong Li (Journal of Hydrology, 2024)

An approach based on a combination of toxicological experiments and in silico predictions to investigate the adverse outcome pathway (AOP) of paraquat neuro-immunotoxicity - Chunhui Zhang; Ge Shi; Qi Meng; Rong Hu; Yang Li; Guiling Hu; Kaidong Wang; Min Huang (Journal of Hazardous Materials, 2024)

Catalytic hydrotreatment of fast pyrolysis liquids from Pine wood using Ru-based catalysts supported on nitrogen-doped carbon materials - Yunhui Xia; Nan Xi; Xinyang Yu; Maohua Luo; Shi Chen; Qinglian Wang; Yixiong Lin; Rong Wang; Hao Li; Jun Yue; Chen Yang; Wang Yin; et al. (Fuel, 2024)

Formation mechanism, environmental sensitivity and functional characteristics of succinylated ovalbumin/ε-polylysine electrostatic complexes: The roles of succinylation modification and ε-polylysine combination - Ru-yi Zhang; Hui-min Zhang; Tian-zhu Guan; Zhi-rong Wang; Hua-xiang Li; Lei Yuan; Yan-jun Yang; Sheng-qi Rao (Food Chemistry, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

Fluoride exposure during puberty induces testicular impairment via ER stress-triggered apoptosis in mice - Rong Wang; Wenjing Gong; Yumeng Jiang; Qizi Yin; Ziyue Wang; Jie Wu; Mingming Zhang; Mengyuan Li; Yehao Liu; Juan Wang; Yuanhua Chen; Yanli Ji (Food and Chemical Toxicology, 2024)

Porphyrin-based MOFs for sensing environmental pollutants - Pan Gao; Soumya Mukherjee; Mian Zahid Hussain; Song Ye; Xusheng Wang; Weijin Li; Rong Cao; Martin Elsner; Roland A Fischer (Chemical Engineering Journal, 2024)

“Edge in-situ heterogeneous” BiOI based on defect engineering and non-noble metal deposition: Boosting visible-light photocatalytic sterilization - Bangfeng Fu; Yifan Pan; Peng Zhao; Liang Zhang; Junchen Zhuo; Jianxing Feng; Bingzhi Li; Lenan Yao; Jiafeng Xi; Xi Lan; Linpin Luo; Ting Du; et al. (Chemical Engineering Journal, 2024)

Water-soluble metal-organic cages crosslinked injectable hydrogel for multi-modal synergistic therapy - Wen-Zhen Li; Xiao-Fan Rong; Yu Wang; Jia-Wen Xiong; Na Zhou; Zi-Xin Wang; Xi-Jia Fang; Wenjing Wang; Yi Liu; Xiao-Qiang Wang (Chemical Engineering Journal, 2024)

The influence of vegetation restoration on soil quality in abandoned farmlands in the Yuanjiang dry-hot valley - Guanghai Wang; Yifan Dong; Li Rong; Wantao Yang; Xingwu Duan (CATENA, 2024)

Multiple scenario land use simulation based on a coupled MOGA-PLUS model: a case of the Yellow River Basin - Guanghui Li; Yinghui Chang; Pengyan Zhang; Qianxu Wang; Zhuo Chen; Xinyue Zhang; Guangrui Xing; Rong Lu; Mengfan Li; Lei Gu (Environmental Science and Pollution Research, 2024)

Functional comparison of Rab3aa and Rab3ab in grass carp (Ctenopharyngodon idella) immune response and GCRV replication - Lifei Luo; Lv Xiong; Cheng Yang; Libo He; Lanjie Liao; Yongming Li; Zuoyan Zhu; Yaping Wang; Rong Huang (Aquaculture, 2024)

NCOA4-mediated ferritinophagy participates in cadmium-triggered ferroptosis in spermatogonia - Didi Jia; Mingming Zhang; Mengyuan Li; Wenjing Gong; Wei Huang; Rong Wang; Yihang Chen; Qizi Yin; Jie Wu; Zhongxiu Jin; Juan Wang; Yehao Liu; et al. (Toxicology, 2024)

Enhanced ammonia oxidation by a photoelectrocatalysis‑chlorine system: The role of ClO• and free chlorine - Xiaodan Wang; Xi Ma; Yaoyao Wu; Chuanhao Li; Rong Chen (Science of The Total Environment, 2024)

Centennial-scale cooling-induced megadroughts in Myanmar's tropical arid region over the past 8000 years - Jie Li; Jiaoyang Zhang; Jingjing Li; Miaofa Li; Jixiang Liu; Bob Hudson; Kyaing Sein; Huiling Zhang; Rong Wang; Luo Wang; Guoqiang Chu; Jule Xiao (Quaternary Science Reviews, 2024)

A Pennsylvanian rugose coral assemblage from eastern Junggar Basin, Northwest China - Sun-Rong Yang; Le Yao; Zhang-Shuai Hou; Xun-Yan Ye; Ying Li; Xing Huang; Shu-Zhong Shen; Xiang-Dong Wang (Palaeoworld, 2024)

OsPRMT6a-mediated arginine methylation of OsJAZ1 regulates jasmonate signaling and spikelet development in rice - Kun Dong; Fuqing Wu; Siqi Cheng; Shuai Li; Feng Zhang; Xinxin Xing; Xin Jin; Sheng Luo; Miao Feng; Rong Miao; Yanqi Chang; Shuang Zhang; et al. (Molecular Plant, 2024)

Multistage dolomitization influenced by the Emeishan large igneous province: Petrographical and geochemical evidence - Yang Li; Xiyan Yang; Xinzhi Wang; Cunhui Fan; Xiangyu Fan; Yu Zhang; Rong Yang; Yue Li; Zisang Huang; Fei Huo (Marine and Petroleum Geology, 2024)

Inactivation of microorganisms on fabrics using plasma-activated nebulized mist driven by different plasma gases - Pengyu Zhao; Sihong Ma; Li Guo; Yikang Jia; Rui Zhang; Min Chen; Zifeng Wang; Dingxin Liu; Yuan Zhao; Xiaohua Wang; Mingzhe Rong (Journal of Hazardous Materials, 2024)

Long-term residue returning increased subsoil carbon quality in a rice-wheat cropping system - Yinan Xu; Yalin Yu; Jing Sheng; Yuekai Wang; Haishui Yang; Feng-Min Li; Shiping Liu; Zheng-Rong Kan (Journal of Environmental Management, 2024)

ZnO nanorod coatings attenuate antibiotic resistance genes (ARGs) on their surface biofilms in estuarine environment - Xing-pan Guo; Rong-rong Sha; Yu-cen Wang; Jia Yan; Bo Peng; Zuo-shun Niu; Wen-liang Liu; Xin Li; Yi Yang (Journal of Environmental Chemical Engineering, 2024)

Metabolome and transcriptome reveal high abundance of bioactive substances in albino jujube fruit as potential function food - Yang Wang; Yong Huang; Panhui Song; Xuemei Peng; Xinyu Li; Rong Su; Hui Zhang; Lijin Lin; Hui Xia; Qunxian Deng (Food Bioscience, 2024)

Effects of carnosine combined with Lactobacillus on the antioxidant capacity of liver and kidney in normal or stressed mice - Jian Qin; Yue Ma; Conghui Wang; Huiying Li; Zhiqiang Zou; Yunqing Zhang; Jing Ma; Rong Du (Food Bioscience, 2024)

Prospective findings from the Dongfeng-Tongji cohort: Exposure to various metals, the expression of microRNA-4286, and the incidence of acute coronary syndrome - Miaoyan Shen; Xuedan Xu; Wending Li; Xi Wang; Rong Peng; Xuezhen Liu; Qiuhong Wang; Xiaomin You; Pinpin Long; Hao Wang; Rundong Niu; Yu Yin; et al. (Environmental Research, 2024)

Boosting persulfate activation through efficient π → π* transition activated by Cu ion anchored porphyrin-based metal–organic framework - Wen-Qiang Li; Oleksandr Savateev; Yuan-Ming Li; Jian-Kang Zheng; Yi-Xuan Wang; Nannan Hou; Xiao-Cheng Liu; Rong-Rong Ding; Xiao-Guo Zhou; Yang Wang; Xian-Yang Shi; Yang Mu (Chemical Engineering Journal, 2024)

Synergistic chemo-photodynamic therapy based on hollow mesoporous organosilica nanoparticles for reducing psoriasis-like inflammation - Zhijia Fan; Gang Zhao; Yixiao Gan; Li Wei; Rong Xia; Min Lu; Zhicheng Wang (Chemical Engineering Journal, 2024)

Hydrophilic phthalocyanine covalent organic frameworks for enhanced electrocatalytic H2O2 production - Rong Jiang; Qianjun Zhi; Bin Han; Ning Li; Kang Wang; Dongdong Qi; Wenjun Li; Jianzhuang Jiang (Chemical Engineering Journal, 2024)

Construction and applications of hybrid nanochannels with helical foldamers and solid-state nanopores - Fupeng Qin; Mengqi Sheng; Rongjie Li; Daixin Liu; Meili Ren; Rong Tian; Lyes Douadji; Deqiang Wang; Quan Gan; Liyuan Liang (Chemical Engineering Journal, 2024)

A nonlinear elastic-strain hardening model for frozen improved sandy soil under uniaxial compression loading condition - Bo Liu; Yanqing He; Yanhui Han; Guoxuan Wang; Rong Gao; Dongyang Li (Cold Regions Science and Technology, 2024)

A compound enzyme as an additive to a continuous anaerobic dynamic membrane bioreactor for enhanced lignocellulose removal from codigestion: Performance, membrane characteristics and microorganisms - Bao-Shan Xing; Xiang-Lin Chang; Yi Zhang; Sifan Cao; Xi-Fang Tang; Yong-Chen Han; Yu-You Li; Xiaochang C. Wang; Rong Chen (Bioresource Technology, 2024)

Chemical constituents from Albatrellus confluence and their chemotaxonomic significance - Qing-Fang Wang; Jing-Rong Ou-Yang; Ting-Ting Guo; Ming-Ming Li; Hong-Ping He (Biochemical Systematics and Ecology, 2024)

Chemical constituents of the deep-sea-derived fungus Trichoderma simmonsii ZEN3 and their chemotaxonomic significance - Li-Fang Liu; Yuan Wang; Rong Chao; Lin Xu; Zheng-Biao Zou; Kai Zhang; Ming-Min Xie; Xian-Qiang Chen; Cheng-Hai Gao; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Fibroblast-localized lncRNA CFIRL promotes cardiac fibrosis and dysfunction in dilated cardiomyopathy - Shuai Yuan; Xudong Zhang; Jiabing Zhan; Rong Xie; Jiahui Fan; Beibei Dai; Yanru Zhao; Zhongwei Yin; Qian Liu; Dao Wen Wang; Huaping Li; Chen Chen (Science China Life Sciences, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Genome-wide analysis of in vivo-evolved Candida auris reveals multidrug-resistance mechanisms - Xin-Fei Chen; Han Zhang; Ling-Li Liu; Li-Na Guo; Wen-Jing Liu; Ya-Li Liu; Ding-Ding Li; Ying Zhao; Ren-Yuan Zhu; Yi Li; Rong-Chen Dai; Shu-Ying Yu; et al. (Mycopathologia, 2024)

Viperin inhibits interferon-γ production to promote Mycobacterium tuberculosis survival by disrupting TBK1-IKKε-IRF3-axis and JAK-STAT signaling - Yao Liang; Yun Liang; Qi Wang; Qianna Li; Yingqi Huang; Rong Li; Xiaoxin Pan; Linmiao Lie; Hui Xu; Zhenyu Han; Honglin Liu; Qian Wen; et al. (Inflammation Research, 2024)
Objectives and design As an interferon-inducible protein, Viperin has broad-spectrum antiviral effects and regulation of host immune responses. We aim to investigate how Viperin regulates interferon-γ (IFN-γ) production in macrophages to control Mycobacterium tuberculosis (Mtb) infection. Methods We use Viperin deficient bone-marrow-derived macrophage (BMDM) to investigate the effects and machines of Viperin on Mtb infection. Results Viperin inhibited IFN-γ production in macrophages and in the lung of mice to promote Mtb survival. Further insight into the mechanisms of Viperin-mediated regulation of IFN-γ production revealed the role of TANK-binding kinase 1 (TBK1), the TAK1-dependent inhibition of NF-kappa B kinase-epsilon (IKKε), and interferon regulatory factor 3 (IRF3). Inhibition of the TBK1-IKKε-IRF3 axis restored IFN-γ production reduced by Viperin knockout in BMDM and suppressed intracellular Mtb survival. Moreover, Viperin deficiency activated the Janus kinase (JAK)-signal transducer and activator of transcription (STAT) signaling pathway, which promoted IFN-γ production and inhibited Mtb infection in BMDM. Additionally, a combination of the anti-TB drug INH treatment in the absence of Viperin resulted in further IFN-γ production and anti-TB effect. Conclusions This study highlights the involvement of TBK1-IKKε-IRF3 axis and JAK-STAT signaling pathways in Viperin-suppressed IFN-γ production in Mtb infected macrophages, and identifies a novel mechanism of Viperin on negatively regulating host immune response to Mtb infection.

A Novel FD3 Framework for Carbon Emissions Prediction - Houtian He; Tongyan Liu; Qianqian Li; Jiaru Yang; Rong-Long Wang; Shangce Gao (Environmental Modeling & Assessment, 2024)

Dynamic causal modeling analysis reveals the modulation of motor cortex and integration in superior temporal gyrus during multisensory speech perception - Ting Zou; Liyuan Li; Xinju Huang; Chijun Deng; Xuyang Wang; Qing Gao; Huafu Chen; Rong Li (Cognitive Neurodynamics, 2024)
The processing of speech information from various sensory modalities is crucial for human communication. Both left posterior superior temporal gyrus (pSTG) and motor cortex importantly involve in the multisensory speech perception. However, the dynamic integration of primary sensory regions to pSTG and the motor cortex remain unclear. Here, we implemented a behavioral experiment of classical McGurk effect paradigm and acquired the task functional magnetic resonance imaging (fMRI) data during synchronized audiovisual syllabic perception from 63 normal adults. We conducted dynamic causal modeling (DCM) analysis to explore the cross-modal interactions among the left pSTG, left precentral gyrus (PrG), left middle superior temporal gyrus (mSTG), and left fusiform gyrus (FuG). Bayesian model selection favored a winning model that included modulations of connections to PrG (mSTG → PrG, FuG → PrG), from PrG (PrG → mSTG, PrG → FuG), and to pSTG (mSTG → pSTG, FuG → pSTG). Moreover, the coupling strength of the above connections correlated with behavioral McGurk susceptibility. In addition, significant differences were found in the coupling strength of these connections between strong and weak McGurk perceivers. Strong perceivers modulated less inhibitory visual influence, allowed less excitatory auditory information flowing into PrG, but integrated more audiovisual information in pSTG. Taken together, our findings show that the PrG and pSTG interact dynamically with primary cortices during audiovisual speech, and support the motor cortex plays a specifically functional role in modulating the gain and salience between auditory and visual modalities.

Exogenous carbon addition soil mediated phosphorus dynamics under eight years continuous input of swine manure in a wheat-rice rotation - Chunlong Zhang; Xiaoyan Tang; Changquang Wang; Edith le Cadre; Rong Huang; Qi Tao; Yingjie Wu; Youlin Luo; Qiang Xu; Genchuan Bai; Bing Li (Agriculture, Ecosystems & Environment, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

CYTOR-NFAT1 feedback loop regulates epithelial-mesenchymal transition of retinal pigment epithelial cells - Rong Zhang; Lin Wang; Yang Li; Yan Liu; Kui Dong; Yajing Pei; Junmei Zhao; Gang Liu; Jing Li; Xiaodan Zhang; Tong Cui; Yan Gao; et al. (Human Cell, 2024)

Responses of phenology to preseason drought and soil temperature for different land cover types on the Mongolian Plateau - Bing Li; Rong Wang; Jing M. Chen (Science of The Total Environment, 2024)

Northward shift of Indian summer monsoon and intensifying winter westerlies cause stronger precipitation seasonality over Pamirs and its downstream basins in the 21st century - Jinping He; Keqin Duan; Shuangshuang Li; Wei Shang; Qiong Wang; Rong Chen; Yali Meng (Science of The Total Environment, 2024)

Synergistic effects of biochar addition and filtration mode optimization on mitigating membrane fouling in high-solid anaerobic membrane bioreactors - Chengfan Jiao; Hao Chen; Yaqian Liu; Hexiang Zhao; Qian Li; Gaojun Wang; Rong Chen; Yu-You Li (Science of The Total Environment, 2024)

Advances in understanding bioaerosol release characteristics and potential hazards during aerobic composting - Sai Yang; Yanan Yin; Wenrong Zhang; Haichao Li; Xiaochang Wang; Rong Chen (Science of The Total Environment, 2024)

Neural network establishes co-occurrence links between transformation products of the contaminant and the soil microbiome - Yuhui Xiang; Yansong Yu; Jiahui Wang; Weiwei Li; Yu Rong; Haibo Ling; Zhongbing Chen; Yiguang Qian; Xiaole Han; Jie Sun; Yuyi Yang; Liang Chen; et al. (Science of The Total Environment, 2024)

Massive early Middle Pleistocene cheetah from eastern Asia shed light onto the evolution of Acinonyx in Eurasia - Qigao Jiangzuo; Yaming Wang; Joan Madurell-Malapeira; Saverio Bartolini Lucenti; Shijie Li; Shiqi Wang; Zhaoyu Li; Rong Yang; Yi Jia; Lu Zhang; Shanqin Chen; Changzhu Jin; et al. (Quaternary Science Reviews, 2024)

A literature review on phosphate removal from wastewater by lanthanum-based adsorbents: From mechanisms to applications - Yao-Yao Lu; Hao Wang; Rong-Rong Chang; Wen-Bing Li; Bao-Cheng Huang; Ren-Cun Jin (Journal of Water Process Engineering, 2024)

The separate and synergistic role of biochar and electric field to facilitate mesophilic anaerobic digestion of food waste slurry - Gaojun Wang; Bo Zhang; Changxi Sun; Lu Chen; Kexin Wang; Qian Li; Rong Chen (Journal of Water Process Engineering, 2024)

Enhanced atomic H* utilization on urchin-like TiO2-supported palladium nanoparticles for efficient electrocatalytic detoxification of chlorinated organics - Jun Zhang; Shuyue Liu; Shiyu Lu; Chunyuan Wang; Pingjuan Liang; Huan Yi; Mengjie Li; Laizheng Luo; Rong Wang; Guangming Jiang (Fuel, 2024)

Modifying duck myofibrillar proteins using sodium bicarbonate under cold plasma treatment: Impact on the conformation, emulsification, and rheological properties - Shengqi Jiang; Chunjie Yang; Rong Bai; Ziwei Li; Linlu Zhang; Ya Chen; Xiang Ye; Siying Wang; Hao Jiang; Wu Ding (Food Hydrocolloids, 2024)

hOGG1: A novel mediator in nitrosamine-induced esophageal tumorigenesis - De-Rong Tang; Cheng-Lin Li; Zhi-Yun Xu; Zhen-Zhong Zhang; Qian-Wei Wang; Jian-Qiang Zhao (Food and Chemical Toxicology, 2024)

Expression analysis and antiviral activity of koi carp (Cyprinus carpio) viperin against carp edema virus (CEV) - Xiao-wen Wang; Rong Zhang; Li-li Liu; Hui-juan Li; Hua Zhu (Fish & Shellfish Immunology, 2024)

Phosphorylated covalent organic framework/graphene composites for photoelectrothermal integrated collaborative reduction of uranium - Rui Zhang; Liang Tao; Cheng-Peng Niu; Cheng-Rong Zhang; Tie-Ying Shi; Xiao-Xing Wang; Ying-Ao Wang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

A site distance dependence of product selectivity in n-hexane dehydrogenation over alumina-supported chromium catalyst - Xiuyi Li; Rong Fan; Haowei Shen; Guowei Wang; Chunyi Li (Chemical Engineering Journal, 2024)

Unravelling the safety improving and failure mechanisms of a 56.5 Ah high-energy–density Li-ion cell containing solid-state electrolyte - Wei Zhang; Xiaopeng Qi; Min Liu; Bingxue Liu; Yuansen Hu; Jing Ye; Rennian Wang; Bin Li; Changhong Wang; Qian Huang; Bing Yu; Rong Yang; et al. (Chemical Engineering Journal, 2024)

A new substrate equalization method for optimizing the influent conditions and fluid flow patterns of a multifed upflow anaerobic sludge blanket reactor with mature anammox granules - Bao-Shan Xing; Xi-Fang Tang; Ling-Hu Li; Yu-Lin Fu; Jia-Yi Liu; Ya-Ge Wang; Xin-Xin Sun; Yu-You Li; Rong Chen; Ren-Cun Jin (Bioresource Technology, 2024)

Enhancing biohydrogen production from xylose through natural FeS2 ore: Mechanistic insights - Yun Xu; Miao-yu Deng; Si-jia Li; Yi-cheng Yuan; Hao-yu Sun; Quan Wang; Rong-ping Chen; Lei Yu (Bioresource Technology, 2024)

Ceria nanoparticles: biomedical applications and toxicity - Xiaoxuan Fu; Peng Li; Xi Chen; Yuanyuan Ma; Rong Wang; Wenxuan Ji; Jiakuo Gu; Bowen Sheng; Yizhou Wang; Zhuhong Zhang (Journal of Zhejiang University-SCIENCE B, 2024)

Ginsenoside Rg1 Alleviates Sepsis-Induced Acute Lung Injury by Reducing FBXO3 Stability in an m6A-Dependent Manner to Activate PGC-1α/Nrf2 Signaling Pathway - Rong Liu; Qiang Wang; Yao Li; Ruixue Wan; Ping Yang; Dexing Yang; Jiefu Tang; Jiafei Lu (The AAPS Journal, 2024)

Long-Term Spatiotemporal Characteristics of Ulva prolifera Green Tide and Effects of Environmental Drivers on Its Monitoring by Satellites: A Case Study in the Yellow Sea, China, from 2008 to 2023 - Yating Zhan; Zhongfeng Qiu; Yujun Wang; Yiming Su; Yin Li; Yanmei Cui; Shuai Qu; Peng Wang; Xin Rong (Journal of Marine Science and Engineering, 2024)
Ulva prolifera (U. prolifera) green tide outbreaks have occurred in the Yellow Sea of China for many years, causing serious losses to marine ecology and the marine economy. The monitoring and tracking of U. prolifera green tide is a crucial aspect of marine ecological disaster prevention and control management. This paper aims to investigate the spatiotemporal distribution changes in U. prolifera green tide in the Yellow Sea throughout its life cycle. A survey of the Yellow Sea from 2008 to 2023 was conducted using multi-source remote sensing images. Long-term monitoring and analysis of U. prolifera revealed the evolution process of the green tide, including the early development, outbreak, decline, and extinction stages, considering time, space, and frequency of occurrence. Additionally, this study examined peak coverage change patterns over the past 16 years and analyzed the influence of environmental factors such as sea surface temperature and sea surface wind field on the development of U. prolifera. The research results serve as a valuable reference for the monitoring, early warning, and scientific prevention and control of U. prolifera green tide in the Yellow Sea, as well as other similar marine disaster areas.

Metabolomics provides insights into the alleviating effect of dietary Caulerpa lentillifera on diquat-induced oxidative damage in zebrafish (Danio rerio) liver - Xiang Lin; Zhongqun Liu; Ye Xiao; Xiaocen Xie; Yongqiang Wang; Haiping Li; Rong Wang; Xi Xie; Yingxia Zhang; Yanting Song; Wenting Hu (Aquaculture, 2024)

PBA alleviates cadmium-induced mouse spermatogonia apoptosis by suppressing endoplasmic reticulum stress - Rong Wang; Mengyuan Li; Zhen Wu; Wenjing Gong; Mingming Zhang; Yehao Liu; Yuyou Yao; Yanli Ji (Toxicology in Vitro, 2024)

Advances in ionogels for proton-exchange membranes - Yilin Zhou; Bei Wang; Zhiwei Ling; Qingting Liu; Xudong Fu; Yanhua Zhang; Rong Zhang; Shengfei Hu; Feng Zhao; Xiao Li; Xujin Bao; Jun Yang (Science of The Total Environment, 2024)

A specific module of ESCRT regulates STING activity termination by controlling STING degradation - Yuan Zhao; Chenxuan Zhou; Wenmin Tian; Yang Chen; Chongchong Zhao; Yan Li; Shixuan Wang; Yueguang Rong (Science Bulletin, 2024)

The double-edged effects of La2O3 and CeO2 on the performance of high-rate anaerobic sludge bed reactors and microbial mechanisms - Kai Su; Lin-xiao Li; Zhuo Zeng; Xue Yang; Tao Lei; Han Zhang; Qin Wang; Rong Cao (Process Safety and Environmental Protection, 2024)

ALKBH5 SUMOylation-mediated FBXW7 m6A modification regulates alveolar cells senescence during 1-nitropyrene-induced pulmonary fibrosis - Se-Ruo Li; Ning-Ning Kang; Rong-Rong Wang; Meng-Die Li; Li-Hong Chen; Peng Zhou; De-Xiang Xu; Hui Zhao; Lin Fu (Journal of Hazardous Materials, 2024)

Investigation of pathogen-laden aerosol aerodynamics and ventilation rates on their long-range transmission: A study on the Fangcang shelter hospital - Chuan Jiang; Zhijian Liu; Yongxin Wang; Guangpeng Yao; Shiyue Li; Rui Rong; Zhenyu Liang; Haiyang Liu; Jingwei Liu; Tongliang Wan; Junzhou He (Journal of Cleaner Production, 2024)

Biochar-mediated synergistic promotion of DIET and IHT: Kinetic and thermodynamic insights into propionate two-step syntrophic methanogenesis - Danyang Zhao; Peiyun Zhang; Yaqian Liu; Qian Li; Gaojun Wang; Rong Chen; Yu-You Li (Chemical Engineering Journal, 2024)

Coculture of Chlorella protothecoides and Coccomyxa subellipsoidea enhances cell growth and lipid accumulation: An effective strategy for biodiesel production - Yuqin Li; Yuanyuan Luo; Rong Zhou; Xiaohong Zuo; Yong Zhang; Zhenyao Wang; Xuan Li; Xing Zhang; Zihao Qin; Carol Sze Ki Lin (Chemical Engineering Journal, 2024)

A robust Zr(IV)-based metal-organic framework featuring high-density free carboxylic groups for efficient uranium recovery - Bin Wang; Chunyu Bao; Jiahui Xu; Yunnan Tao; Long Chen; Duo Zhang; Kui Tan; Shuao Wang; Jian-Rong Li; Shengqian Ma (Chemical Engineering Journal, 2024)

In-situ GSH-responsive gas nanogenerator for active NIR-II FL/PA imaging and synergistic restoration the macrophage niche in rheumatoid arthritis - Xiaochun Zheng; Weiwei Kang; Yarong Jin; Xin Zhang; Wenxuan Wang; Dongsheng Li; Shutong Wu; Lin Chen; Shichao Meng; Rong Dai; Ziliang Zheng; Ruiping Zhang (Chemical Engineering Journal, 2024)

Fine mapping and candidate gene analysis of qSRC3 controlling the silk color in maize (Zea mays L.) - Xueying Wang; Yang Zhou; Chong You; Jinchang Yang; Zhengjie Chen; Dengguo Tang; Jixing Ni; Peng Li; Le Wang; Kaili Zhu; Wujiao Deng; Haimei Wu; et al. (Theoretical and Applied Genetics, 2024)

Evolution of Permeability and Gas Seepage in Deep Coal Under 3D Stress - Tenglong Rong; Pengju Liu; Jiawei Wang; Xiaojian Ren; Xianzhong Li; Guoying Wang (Natural Resources Research, 2024)

Cultivation mode of Saccharina japonica impacts planktonic and epiphytic microbiomes - Yongwei Yan; Shanshan Wang; Shaojun Pang; Kuimei Liu; Lirong Chang; Xiaojun Rong; Jie Li (Algal Research, 2024)

Modulation of plasmacytoid dendritic cell and CD4+ T cell differentiation accompanied by upregulation of the cholinergic anti-inflammatory pathway induced by enterovirus 71 - Li Li; Rong-Wei Huang; Xiao-Ning Liu; Xiao-Yi Xiang; Yuan-Tao Zhou; Xing-Xing Feng; Lv-Yuan Tao; Jia Yu; Qin Yi; Yan-Chun Wang; Xiao-Mei Liu (Archives of Virology, 2024)

Copper-doped Lanthanide Coordination Polymers as Luminescent Nanoenzyme for Ratiometric Sensing of H2O2 and Glutathione - Xinru Wu; Chen Ruan; Xinyue Zhu; Lina Zou; Rong Wang; Gaiping Li (Journal of Fluorescence, 2024)

Three new diterpenoids isolated from Euphorbia nematocypha Hand.-Mazz and their anti-fungal activity - Rong-Shuai Li; Zhi-Chang Xu; Ding-Mei Qin; Jia-Bi Huang; Meng-Ru Wang; Xue-Rong Zhao; Quan-Yu Yang; Wei-Lie Xiao; Rui-Rui Wang; Xiao-Li Li (Natural Product Research, 2024)

Adsorption characteristics of Ag+ on sphalerite surface: a combined experimental and first-principle study - Heng Yu; Hongliang Zhang; Chenyang Zhang; Wei Sun; Mingjun Han; Rong Wang; Xin Wei; Songjiang Li (Environmental Science and Pollution Research, 2024)

Generation of golden goldfish Carassius auratus via tyrosinase gene targeting by CRISPR/Cas9 - Huijuan Li; Xiaowen Wang; Rong Zhang; Lili Liu; Hua Zhu (Aquaculture, 2024)

Dietary creatine promotes creatine reserves, protein deposition, and myofiber hyperplasia in muscle of juvenile largemouth bass (Micropterus salmoides) - Haodong Yu; Ya He; Mu Qin; Li Wang; Keming Rong; Xuezhen Zhang (Aquaculture, 2024)

Artificial infection pathway of largemouth bass LMBV and identification of resistant and susceptible individuals - Ya Zhang; Bin Gui; Zhihui Jia; Yongming Li; Lanjie Liao; Zuoyan Zhu; Yaping Wang; Rong Huang (Aquaculture, 2024)

Phytoremediation and environmental effects of three Amaranthaceae plants in contaminated soil under intercropping systems - Rong Huang; Chen Xing; Yuanru Yang; Wang Yu; Liangbin Zeng; Yanqiong Li; Zhijian Tan; Zhian Li (Science of The Total Environment, 2024)

Underlying the inhibition mechanisms of sulfate and lincomycin on long-term anaerobic digestion: Microbial response and antibiotic resistance genes distribution - Li Xie; Jiaxin Zhu; Jing Xie; Jun Xu; Rong He; Wenbiao Wang (Science of The Total Environment, 2024)

Cypermethrin induces Sertoli cell apoptosis through endoplasmic reticulum-mitochondrial coupling involving IP3R1-GRP75-VDAC1 - Rui Zhang; Xu-Xu Wang; Jia-fei Xie; Ting-ting Yao; Qian-wen Guo; Qi Wang; Zhen Ding; Jin-Peng Zhang; Mei-Rong Zhang; Li-Chun Xu (Reproductive Toxicology, 2024)

Tsaokoflavanols A1–J1: Flavanol-fatty alcohol hybrids with HPL inhibitory activity from Amomum tsao-ko - Tian-Rong Yang; Shi-Chao Huang; Yun-Fen Wang; Zai-Xiang Lou; Shao-Xing Dai; Li-Hua Su; Min Xu (Phytochemistry, 2024)

Reservoir characteristics and controlling factors of the middle–high maturity multiple lithofacies reservoirs of the Lianggaoshan Formation shale strata in the northeastern Sichuan basin, China - Xin Wang; Min Wang; Chen Zhao; Xinyi Yang; Yidong Jia; Rong Wu; Tianyi Li; Xinbin Zhao; Yulong Tang (Marine and Petroleum Geology, 2024)

Multistage and diverse melt-mantle interaction in dunite-harzburgite channel systems beneath oceanic slow-ultraslow spreading centers: Evidence from the Xigaze ophiolite (Tibet) - Li Wang; Qing Xiong; Jian-Ping Zheng; Hong-Kun Dai; Lian-Rong Tian; Xiang Zhou (Lithos, 2024)

Geomorphic expression of transverse drainages across the Tugerming anticline, southern Tian Shan: Implications for the river-fold interaction in the foreland - Feng Li; Xuhua Shi; Julien Charreau; Xiaogan Cheng; Rong Yang; Hanlin Chen; Jin Ge; Jinghan Wang (Journal of Structural Geology, 2024)

Integrated morphological, physiological and transcriptomic analyses reveal response mechanisms of rice under different cadmium exposure routes - Qin Dong; Yingjie Wu; Haidong Wang; Bing Li; Rong Huang; Huanxiu Li; Qi Tao; Qiquan Li; Xiaoyan Tang; Qiang Xu; Youlin Luo; Changquan Wang (Journal of Hazardous Materials, 2024)

Development and validation of an in situ high-resolution technique for measuring antibiotics in sediments - Yanying Li; Qiuyu Rong; Chao Han; Hanbing Li; Jun Luo; Liying Yan; Degao Wang; Kevin C. Jones; Hao Zhang (Journal of Hazardous Materials, 2024)

Intraparticle sorption and desorption of antibiotics - Cheng Zhang; Rong Li; Dongfang Ke; Hongri Suo; Shuai Wang; Enze Ma; Yulong Chen; Chongxuan Liu (Journal of Hazardous Materials, 2024)

Biochar improves the humification process during pig manure composting: Insights into roles of the bacterial community and metabolic functions - Yanan Yin; Xiaohui Tao; Yifei Du; Mengtong Li; Sai Yang; Wenrong Zhang; Chao Yang; Haichao Li; Xiaochang Wang; Rong Chen (Journal of Environmental Management, 2024)

Kinetics of fe-containing solid waste reduction by carbonaceous materials in CO2 atmosphere: The cause of reducing agent burnout during direct reduction treatment - Xin Li; Guangsheng Wei; Hongyang Wang; Bohan Tian; Rong Zhu; Yefeng Wang (Fuel, 2024)

TiO2-x modified Ni/SBA-15 catalysts for dibenzofuran hydrodeoxygenation - Yu-Kun Wang; Hao-Wei Li; Yu-Rong Liu; Zi-Zheng Xie; Zhen-Yi Du; Xing-Bao Wang; Wen-Ying Li (Chemical Engineering Journal, 2024)

Stereoisomerically enhanced polynorbornene-imide dielectric energy storage performance - Hongmei Qin; Man Liu; Shiyu Qin; Shixian Zhang; Xingnan Zhou; Chenjian Li; Yuhao Wei; Dan Chen; Rong Fan; Shan Wang; Quanling Yang; Chuanxi Xiong; et al. (Chemical Engineering Journal, 2024)

Damming-associated landscape change benefits a wind-dispersed pioneer plant species - Hang Ji; Yong-Rong He; Hong-Yue Li; Ling Lu; Jia-Hui Li; Jie Zou; Rong Wang; Jun-Yin Deng; Xiao-Yong Chen (New Forests, 2024)

Soil Carbon Mineralization and Aggregate Distribution in Various Tillage Practices of Rice–Wheat Cropping System: A Field and Laboratory Study - Naeem Ahmad; Ahmad Latif Virk; Muhammad Bilal Hafeez; Zheng-Rong Kan; Zujiao Shi; Rui Wang; Hafiz Muhammad Waleed Iqbal; Muhammad Ishaq Asif Rehmani; Xiaoli Wang; Rattan Lal; Jun Li (Journal of Soil Science and Plant Nutrition, 2024)

New materials of Pliorhinus ringstroemi from the Linxia Basin (Late Miocene, eastern Asia) and their taxonomical and evolutionary implications - Shijie Li; Oscar Sanisidro; Shiqi Wang; Rong Yang; Tao Deng (Journal of Mammalian Evolution, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Ratiometric G-quadruplex/hemin DNAzymes with low-dosage associative substrates - Rong Lai; Xingli Zeng; Qiuda Xu; Ying Xu; Xueni Li; Yulu Ru; Yilin Wang; Dandan Wang; Xiaoshun Zhou; Yong Shao (Analytica Chimica Acta, 2024)

An empirical method for estimating TBM penetration rate using tunnelling specific energy - Lei She; Cheng-cheng Hu; Yan-long Li; She-rong Zhang; Chao Wang; Yu-jie Wang; Ming-ming He; Shi-min Li; Sheng-le Wang (Tunnelling and Underground Space Technology, 2024)

Epidural administration of large dose of opioid μ receptor agonist may impair cardiac functions and myocardial viability via desensitizing transient receptor potential vanilloid 1 - Xiang Ma; Zheng Guo; Mu-Rong Li; Lu Chen; Xing Zhao; Tian-Qi Wang; Tao Sun (Toxicology and Applied Pharmacology, 2024)

Chronic Pb exposure impairs learning and memory abilities by inhibiting excitatory projection neuro-circuit of the hippocampus in mice - Rong-Xin Zou; Xiaozhen Gu; Chenqing Huang; Hui-Li Wang; Xiang-tao Chen (Toxicology, 2024)

Effects of combined exposure to polystyrene microplastics and 17α-Methyltestosterone on the reproductive system of zebrafish - Weiya Rong; Yue Chen; Zijun Xiong; Haiyan Zhao; Tongyao Li; Qing Liu; Jing Song; Xianzong Wang; Yu Liu; Shaozhen Liu (Theriogenology, 2024)

Performance enhancement of damaged RC structures with viscoelastic dampers: Damage assessment and optimal placement - Zhao-Dong Xu; Yuxuan Tao; Yun Yang; Yao-Rong Dong; Jin Duan; Shihua Li; Hao Wang; Shuai Wang (Soil Dynamics and Earthquake Engineering, 2024)

Pathogen profile of Baiyangdian Lake sediments using metagenomic analysis and their correlation with environmental factors - Rong Xiao; Yanping Hu; Yaping Wang; Junming Li; Congling Guo; Junhong Bai; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Jacquelinne J. Acuña; Wenbin Pan (Science of The Total Environment, 2024)

Evidence for the transportation of aggregated microplastics in the symplast pathway of oilseed rape roots and their impact on plant growth - Sashuang Rong; Shutao Wang; Hongmei Liu; Yuxin Li; Jia Huang; Wanqing Wang; Bing Han; Shiming Su; Wei Liu (Science of The Total Environment, 2024)

Comparative study on anthropogenic impacts on soil PAHs: Accumulation and source apportionment in tourist and industrial cities in Hebei Province, China - Tian Xie; Meie Wang; Rong Jiang; Lei Li; Xinyue Chen; Suriyanarayanan Sarvajayakesavalu; Weiping Chen (Science of The Total Environment, 2024)

Diisoprenyl-cyclohexene-type meroterpenoids from a mangrove endophytic fungus Aspergillus sp. GXNU-Y65 and their anti-nonalcoholic steatohepatitis activity in AML12 cells - Feng Qin; Li Luo; Yu-Chen Liu; Xiang-Long Bo; Fu-Rong Wu; Fan-Fan Wang; Mei-Jing Tan; You-Quan Wei; Xiao-Bing Dou; Cai Yi Wang; Xi-Shan Huang; Heng-Shan Wang (Phytochemistry, 2024)

Experimental and computational study on the adsorption mechanism of silver ions on galena surface - Heng Yu; Hongliang Zhang; Chenyang Zhang; Wei Sun; Mingjun Han; Rong Wang; Xin Wei; Songjiang Li (Journal of Water Process Engineering, 2024)

Composition of DOM along the depth gradients in the paddy field treated with crop straw for 10 years - Rong Huang; Zheng Li; Yi Xiao; Jiang Liu; Tao Jiang; Ouping Deng; Xiaoyang Tang; Yingjie Wu; Qi Tao; Qiquan Li; Youlin Luo; Xuesong Gao; et al. (Journal of Environmental Management, 2024)

Comparing the mechanisms of syntrophic volatile fatty acids oxidation and methanogenesis recovery from ammonia stress in regular and biochar-assisted anaerobic digestion: Different roads lead to the same goal - Gaojun Wang; Peng Fu; Yan Su; Bo Zhang; Mengyuan Zhang; Qian Li; Jianfeng Zhang; Yu-You Li; Rong Chen (Journal of Environmental Management, 2024)

Distribution of organophosphorus pesticides and its potential connection with probiotics in sediments of a shallow freshwater lake - Yanping Hu; Rong Xiao; Yaping Wang; Junming Li; Congling Guo; Junhong Bai; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Javiera Manquian; Wenbin Pan (Journal of Contaminant Hydrology, 2024)

Shale oil potential and mobility in low- to medium-maturity lacustrine shales: A case study of the Yanchang Formation shale in southeast Ordos Basin, China - Huairen Cao; Jun Shi; Zhao-Wen Zhan; Hao Wu; Xiaoyu Wang; Xin Cheng; Haolin Li; Yan-Rong Zou; Ping'an Peng (International Journal of Coal Geology, 2024)

Experiment and dynamic simulation of hydrogen recovery from hydrogen-containing gas mixtures via hydrate-membrane coupling method - Jingbo Gao; Qiang Sun; Jia Luo; Leyan Li; Ninghui Liu; Rong Ma; Hang Zhao; Xiangming Li; Zongyu Qin; Yiwei Wang; Xuqiang Guo (Fuel, 2024)

Calcium ions induced ι-carrageenan-based gel-coating deposited on zein nanoparticles for encapsulating the curcumin - Qingyuan Ge; Shuang Rong; Chenxi Yin; David Julian McClements; Qi Fu; Qi Li; Yahong Han; Fuguo Liu; Suqing Wang; Shuai Chen (Food Chemistry, 2024)

Constructing mesoporous biochar derived from waste carton: Improving multi-site adsorption of dye wastewater and investigating mechanism - Yan-Shan Wang; Tong-Rong Huo; Yan Wang; Jia-Wen Bai; Ping-Ping Huang; Chen Li; Shi-Yu Deng; Hong Mei; Jun Qian; Xiao-Chi Zhang; Chen Ding; Qiu-Yu Zhang; et al. (Environmental Research, 2024)

Rational construction of MOF-on-MOF heterojunction with an array of flexible two-dimensional microsheets for efficient CO2 photoreduction - Bing He; Ying-Jie Wang; Xuefeng Bai; He Bian; Yabo Xie; Rui Li; Jian-Rong Li (Chemical Engineering Journal, 2024)

Reactant enrichment in yolk-shell structured Pd/TiN nanoreactors for boosting electrocatalytic hydrodechlorination performance - Jun Zhang; Chunyuan Wang; Shiyu Lu; Shuyue Liu; Pingjuan Liang; Huan Yi; Mengjie Li; Meng Jin; Rong Wang; Guangming Jiang (Chemical Engineering Journal, 2024)

Preparation of potential organic fertilizer rich in γ-polyglutamic acid via microbial fermentation using brewer's spent grain as basic substrate - Fengqing Wang; Yanmei Chen; Jia Zheng; Can Yang; Li Li; Rong Li; Meilin Shi; Zhongxuan Li (Bioresource Technology, 2024)

Relationships between different types of biochar and N2O emissions during composting based on roles of nosZ-carrying denitrifying bacterial communities enriched on compost and biochar particles - Yanan Yin; Mengjin Gu; Wenrong Zhang; Chao Yang; Haichao Li; Xiaochang Wang; Rong Chen (Bioresource Technology, 2024)

Intercropping with Trifolium repens contributes disease suppression of banana Fusarium wilt by reshaping soil protistan communities - Xiangyu Ren; Zeyuan Zhou; Manyi Liu; Zongzhuan Shen; Beibei Wang; Alexandre Jousset; Stefan Geisen; Mohammadhossein Ravanbakhsh; George A. Kowalchuk; Rong Li; Qirong Shen; Wu Xiong (Agriculture, Ecosystems & Environment, 2024)

Ferroptosis: underlying mechanisms and involvement in neurodegenerative diseases - Yi Wang; HongJing Li; QianXiong He; Rong Zou; JinRui Cai; Lin Zhang (Apoptosis, 2024)

Toxicity of common biocides used in aquaculture to embryos and larvae of Brachymystax tsinlingensis Li - Xing‐chen Guo; Zhi‐peng Chu; Rong‐qun Song; Zhen‐lu Wang; Rui‐jiao Li; Dong‐mei Xiong; Mu‐zi Zhang; Hai‐bo Jiang; Jian Shao (Journal of Fish Biology, 2024)
Brachymystax tsinlingensis Li is a threatened fish species endemic to China. With the problems of environmental factors and seeding breeding diseases, it is important to further improve the efficiency of seeding breeding and the basis of resource protection. This study investigated the acute toxicity of copper, zinc and methylene blue (MB) on hatching, survival, morphology, heart rate (HR) and stress behaviour of B. tsinlingensis . Eggs (diameter: 3.86 ± 0.07 mm, weight: 0.032 ± 0.004 g) of B. tsinlingensis were selected randomly from artificial propagation and developed from eye‐pigmentation‐stage embryos to yolk‐sac stage larvae (length: 12.40 ± 0.02 mm, weight: 0.03 ± 0.001 g) and exposed to different concentrations of Cu, Zn and MB for 144 h in a series of semi‐static toxicity tests. The acute toxicity tests indicated that the 96‐h median lethal concentration (LC 50 ) values of the embryos and larvae were 1.71 and 0.22 mg l −1 for copper and 2.57 and 2.72 mg l −1 for zinc, respectively, whereas the MB LC 50 after 144‐h exposure for embryos and larvae were 67.88 and 17.81 mg l −1 , respectively. The safe concentrations of copper, zinc and MB were 0.17, 0.77 and 6.79 mg l −1 for embryos and 0.03, 0.03 and 1.78 mg l −1 for larvae, respectively. Copper, zinc and MB treatments with concentrations greater than 1.60, 2.00 and 60.00 mg l −1 , respectively, led to a significantly low hatching rate and significantly high embryo mortality ( P −1 led to significantly high larvae mortality ( P P P B. tsinlingensis embryos or larvae might be more resistant to copper, zinc and MB than other members of the Salmonidae family, which benefits their resource protection and restoration.

Disclosing phototransformation mechanisms of decabromodiphenyl ether (BDE-209) in different media by simulated sunlight: Implication by compound-specific stable isotope analysis - Guoguang Wang; Chuanyuan Li; Shuaihao Liu; Ziao Xing; Pengxu Guo; Zixuan Hao; Maojiao Li; Haixia Wang; Guangzhi Rong; Yu Liu (Environmental Science and Pollution Research, 2024)

Associations of legacy perfluoroalkyl and polyfluoroalkyl substances, alternatives, and isomers with gestational diabetes mellitus and glucose homeostasis among women conceiving through assisted reproduction in Shanghai, China - Dandan Mao; Guodong Ding; Zixia Wang; Jiuru Zhao; Hong Li; Xiaoning Lei; Jiaqi Zheng; Yan Zhang; Rong Shi; Tao Yuan; Zhiwei Liu; Yu Gao; et al. (Environmental Science and Pollution Research, 2024)

A pair of new chromone enantiomers from Xylaria nigripes - Jing Li; Yue-Ping Jiang; Lan-Qing Li; Hong-Ping Long; Hai-Tao Liu; Rong Yang; Shao Liu; Wen-Xuan Wang; Ji-Kai Liu (Natural Product Research, 2024)

In situ biomass burning enhanced the contribution of biogenic sources to sulfate aerosol in subtropical cities - Tingting Li; Jun Li; Luhua Xie; Boji Lin; Hongxing Jiang; Rong Sun; Xiao Wang; Ben Liu; Chongguo Tian; Qilu Li; Wanglu Jia; Gan Zhang; et al. (Science of The Total Environment, 2024)

Unraveling the role of Financial Risk, social globalization and Economic Risk towards attaining sustainable environment in China: Does resources curse still holds - Liu Rong; Zhenbo Wang; Zhijun Li (Resources Policy, 2024)

Amino-modified biochar-silica hybrid aerogels with ordered pore structure templated by cellulose nanocrystals for highly efficient and selective CO2 capture - Biao Ji; Xudong Zheng; Zihuai Xu; Sifan Bao; Junwei Wang; Wenyu Weng; Jian Rong; Zhongyu Li (Journal of Cleaner Production, 2024)

A novel approach for evaluating the transport capacity of sandstone carriers and determining effective hydrocarbon migration channels: Application to the Pinghu Slope Belt of the Xihu Depression, East China Sea Basin - Fuwei Wang; Dongxia Chen; Meijun Li; Zhangxin Chen; Qiaochu Wang; Khawaja Hasnain Iltaf; Sha Li; Wenzhi Lei; Mengya Jiang; Yuqi Wang; Lanxi Rong (Journal of Asian Earth Sciences, 2024)

Preparation of size-tunable Fe3O4 magnetic nanoporous carbon composites by MOF pyrolysis regulation for magnetic resonance sensing of aflatoxin B1 with excellent anti-matrix effect - Zhou Xu; Yanqiu Chen; Rong Wang; Maolong Chen; Jian Zhang; Yunhui Cheng; Bangben Yao; Li Yao; Jianguo Xu; Wei Chen (Food Chemistry, 2024)

Exposure levels and determinants of placental polybrominated diphenyl ethers in Chinese pregnant women - Yijun Liu; Yan Xie; Yingkuan Tian; Juan Liao; Derong Fang; Linglu Wang; Rong Zeng; Shimin Xiong; Xingyan Liu; Qing Chen; Ya Zhang; Hongyu Yuan; et al. (Environmental Research, 2024)

Mechanistic insights into synergistic facilitation of copper/zinc ions and dewatered swine manure-derived biochar on anaerobic digestion of swine wastewater - Gaojun Wang; Changxi Sun; Peng Fu; Bo Zhang; Jinglin Zhu; Qian Li; Jianfeng Zhang; Rong Chen (Environmental Research, 2024)

Flexural behavior of wet panel-to-panel groove-and-tongue joints provided with lapped U-bars - Ao Dong; Zhenyu Li; Bin Rong; Changxiang Wang; Zeming Wang; Hui Xu (Engineering Structures, 2024)

Two birds with one stone: A magneto-optical dual-stimuli-responsive intelligent Pickering emulsion for efficient conversion of glucose to 5-hydroxymethylfurfural - Zhong-Qiu Liu; Jia-Liang Guo; Rong-Hua Liang; Feng-Xiang Wang; Zhan-Ku Li; Yujing Liu; Anguo Ying (Chemical Engineering Journal, 2024)

HIF-1α: A potential therapeutic opportunity in renal fibrosis - Disheng Liu; Lu Wang; Wuhua Ha; Kan Li; Rong Shen; Degui Wang (Chemico-Biological Interactions, 2024)

RETRACTED ARTICLE: Liquiritin reduces ferroptosis in doxorubicin-induced cardiotoxicity through targeting SLC7A11/GPX4 pathway - Mei Wang; Meng Liu; Lijing Tang; Lixian Shen; Junhui Xiao; Rong Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

A near-infrared fluorescent probe for viscosity: Differentiating cancer cells from normal cells and dual-modal imaging in tumor mice - Jing-Jing Chao; Hui Zhang; Zhi-Qing Wang; Qiao-Rong Liu; Guo-Jiang Mao; Yongfei Li; Chun-Yan Li (Analytica Chimica Acta, 2024)